Battery monomer, battery and electric device

By using combinations of positive electrode active materials of different crystal types in the positive electrode sheet of the battery and adjusting the anion content in the electrolyte, the problem of increasing internal resistance of the battery is solved, and the battery cycle life is extended and the high energy density is improved.

CN119852303APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311349270.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The internal resistance of existing batteries increases rapidly during cycles, resulting in a decrease in battery power performance attenuation and capacity retention rate, affecting the battery's service life.

Method used

By using a combination of a first positive electrode active material and a second positive electrode active material including different crystal forms in the positive electrode sheet of the battery, and adjusting the anion content in the electrolyte so that it meets a specific weight ratio range, the matching of the positive electrode active material and the acidity of the electrolyte are optimized.

Benefits of technology

It reduces the internal resistance growth rate during the battery cycle, extends the battery's cycle life, and improves the battery's high energy density and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852303A_ABST
    Figure CN119852303A_ABST
Patent Text Reader

Abstract

The invention provides a battery monomer, a battery and a power utilization device. The battery monomer comprises a positive pole piece and an electrolyte, a positive active material comprises a first positive active material and a second positive active material, the electrolyte comprises a non-aqueous solvent, an electrolyte salt and a first additive, the electrolyte salt comprises first cations and first anions, and the first additive comprises second cations and second anions; and the second anion comprises one or two of HPO4 < 2-> and H2PO4 <->. The weight content of the first anions in the electrolyte is recorded as wa, the weight content of the second anions in the electrolyte is recorded as wb, and the weight content wa and the weight content wb are based on the total weight of the electrolyte; based on the total weight of the positive electrode active material, the weight content of the first positive electrode active material is recorded as w1, and the weight content of the second positive electrode active material is recorded as w2; and the battery monomer satisfies 0.99 < = 100 * (w1 / w2) * [wb / (wa + wb)] < = 19.0. The cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As an important component of the battery, the performance of the positive electrode active material will affect the performance of the battery. At present, a single positive electrode active material that can simultaneously meet the requirements of low cost, high gram capacity and few side reactions has not yet been developed, so the positive electrode plate often includes two or more different types of positive electrode active materials at the same time. However, when different types of positive electrode active materials are mixed and used, the internal resistance of the battery increases rapidly during the cycle, which causes the power performance of the battery to decay more greatly and the capacity retention rate to decay faster in the later stage of use, thereby affecting the use of the battery. The above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0003] The present application provides a battery cell, a battery and an electrical device, which can improve the cycle performance of the battery.

[0004] A first aspect of the present application provides a battery cell, comprising a positive electrode plate and an electrolyte.

[0005] The positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material and the second positive electrode active material can extract and embed lithium ions, the first positive electrode active material includes Ni element, the second positive electrode active material includes Fe element, the first positive electrode active material and the second positive electrode active material have different crystal forms, and the specific surface area of ​​the first positive electrode active material is smaller than the specific surface area of ​​the second positive electrode active material.

[0006] The electrolyte includes a non-aqueous solvent, an electrolyte salt, and a first additive, wherein the electrolyte salt includes a first cation and a first anion, the first additive includes a second cation and a second anion, and the second anion includes HPO4 2- 、H2PO4 - One or both of the following.

[0007] The weight content of the first anion in the electrolyte is recorded as w a The weight content of the second anion in the electrolyte is recorded as w b, are based on the total weight of the electrolyte; based on the total weight of the positive electrode active material, the weight content of the first positive electrode active material is recorded as w1, and the weight content of the second positive electrode active material is recorded as w2; and the battery cell satisfies 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0.

[0008] By adjusting the weight content of the first anion in the electrolyte w a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, the amount of the second anion can be better matched with the amount of the first positive electrode active material and the second positive electrode active material, thereby reducing the internal resistance growth rate during the battery cycle, reducing the acidity of the electrolyte, and making the battery have good cycle performance.

[0009] In any embodiment, 1.17≤100×(w1 / w2)×[w b / (w a +w b )]≤16.33, optionally, 2.00≤100×(w1 / w2)×[w b / (w a +w b )]≤11.67. Thus, the amount of the second anion can be better matched with the amount of the first positive electrode active material and the second positive electrode active material, thereby further reducing the internal resistance growth rate and the acidity of the electrolyte during the battery cycle, so that the battery has better cycle performance.

[0010] In any embodiment, w1 is 33.5%-95%, optionally, w1 is 50%-70%.

[0011] In any embodiment, w2 is 5%-66.5%, optionally, w2 is 30%-50%.

[0012] By adjusting the weight content w1 of the first positive electrode active material and / or the weight content w2 of the second positive electrode active material within the above range, the battery can have both high energy density and long cycle life.

[0013] In any embodiment, 0.5%≤w b / (w a +wb )≤5.5%, optionally, 1.5%≤w b / (w a +w b )≤4.5%.

[0014] In any embodiment, the specific surface area of ​​the first positive electrode active material is 0.5-1 m 2 / g, optional 0.6-0.9m 2 / g.

[0015] In any embodiment, the specific surface area of ​​the second positive electrode active material is 11-18.4 m 2 / g, optional 11.9-15.0m 2 / g.

[0016] In any embodiment, the first cation comprises a lithium ion.

[0017] In any embodiment, the first anion comprises PF6 - 、ClO4 - 、AsF6 - 、BF4 - 、N(CF3SO2)2 - CF3SO3 - 、N(FSO2)2 - 、C(SO2CF3)3 - PO2F2 - , one or more of difluorooxalatoborate ion, dioxalatoborate ion, difluorooxalatophosphate ion, and tetrafluorooxalatophosphate ion.

[0018] In any embodiment, the second cation includes one or more of lithium ions and Me ions, and the Me ions include one or more of sodium ions, potassium ions, calcium ions, and magnesium ions.

[0019] In any embodiment, the weight content of Ni element in the positive electrode film layer is recorded as w Ni , based on the total weight of the positive electrode film layer, 10.2%≤w Ni ≤28.8%, optionally, 15.1%≤w Ni ≤21.2%.

[0020] In any embodiment, the weight content of Fe element in the positive electrode film layer is recorded as w Fe , based on the total weight of the positive electrode film layer, 1.2% ≤ w Fe ≤11.1%, optionally, 3.9%≤w Fe ≤8.7%.

[0021] By adjusting the weight content of the Ni element and / or the Fe element within the above range, the battery can have both high energy density and long cycle life.

[0022] In any embodiment, the first positive active material includes a lithium-containing layered oxide.

[0023] In any embodiment, the first positive electrode active material includes a compound represented by formula (I).

[0024] Li a A 1 b Ni c Co d B 1 e C 1 f O g D 1 h (I)

[0025] A 1 It includes one or more elements selected from Group IA, Group IIA, Group VIII, Group VIB, and Group IIB, and may optionally include one or more elements selected from Na, K, Mg, Rb, Zn, and Zr; B 1 including Mn and / or Al; C 1 The invention comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB and Group VIII, and may be selected from Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Cu, Ba, Mo, V, Ce, Nb, Sb, Ta, Ge, Nb, Sc, Ba, B, S and Y, and may be selected from Mg, Ti, W, Zr, Cr, Zn, Cu, V, Nb, Sr, Sb and Y. 1It includes one or more elements selected from Group VIA and Group VIIA, and can be selected from one or more elements selected from N, S, F, Cl and Br, and can be selected from S and / or F; a is selected from the range of 0.75 to 1.2, and can be selected from the range of 0.9 to 1.1; b is selected from the range of 0 to 0.2, and can be selected from the range of 0 to 0.1; c is selected from the range of 0.500 to 0.990, and can be selected from the range of 0.500 to 0.600; d is selected from the range of 0 to 0.490, and can be selected from the range of 0 to 0.100; e is selected from the range of 0.001 to 0.490, and can be selected from the range of 0.300 to 0.450; f is selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.05; g is selected from the range of 1.0 to 2.0, and can be selected from the range of 1.9 to 2.0; h is selected from the range of 0 to 1.0, and can be selected from the range of 0.01 to 0.1.

[0026] In any embodiment, c+d+e+f=1.

[0027] In any embodiment, g+h=2.

[0028] In any embodiment, the first positive electrode active material includes a first core and a first shell covering the first core, the first core includes a compound represented by formula (I); the first shell includes one or more coating layers, each coating layer has ionic conductivity and / or electronic conductivity.

[0029] In any embodiment, the one or more coating layers independently include one or more selected from phosphate, pyrophosphate, carbon, doped carbon, oxide, and fast ion conductor, and can optionally include one or more selected from phosphate, pyrophosphate, and oxide.

[0030] In any embodiment, the coating amount of the first shell is 0.005-1% by weight, and optionally 0.01-0.5% by weight, based on the weight of the first core.

[0031] In any embodiment, the thickness of the first shell is 2-200 nm, and optionally 5-50 nm.

[0032] In any embodiment, the second positive active material includes a lithium-containing phosphate.

[0033] In any embodiment, the second positive electrode active material includes a compound represented by formula (II).

[0034] Li m1 A 2 x1 Mn 1-y1-y2 Fe y2 B 2y1 P 1-z1 C 2 z1 O 4-n1 D 2 n1 (II)

[0035] A 2 It includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB and Group VIB, and may be selected from one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and may be selected from one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; B 2 The invention comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB and Group VIII, and may be selected from one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge; C 2 It includes one or more elements selected from Group IIIA, Group IVA, Group VA and Group VIA, and may optionally include one or more elements selected from Group B, S, Si and N; D 2The invention comprises one or more elements selected from Group VIA and Group VIIA, and may be selected from one or more elements selected from S, F, Cl and Br; m1 is selected from the range of 0.85 to 1.15, may be selected from the range of 0.9 to 1.1, and may be selected from the range of 0.97 to 1.01; x1 is selected from the range of 0 to 0.1, may be selected from the range of 0.001 to 0.1, and may be selected from the range of 0.001 to 0.005; y1 is selected from the range of 0 to 0.5, may be selected from the range of 0.001 to 0.5, and may be selected from the range of 0.005 to 0.2 range; y2 is selected from the range of 0.1 to 1, and can be selected from the range of 0.2 to 0.9, and can be selected from the range of 0.3 to 0.7; 1-y1-y2 is selected from the range of 0 to 0.9, and can be selected from the range of 0.05 to 0.75, and can be selected from the range of 0.22 to 0.68; z1 is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1, and can be selected from the range of 0.001 to 0.005; n1 is selected from the range of 0 to 0.5, and can be selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.005.

[0036] By doping specific elements in specific amounts at the transition metal position, Li position, P position and / or O position of the lithium-containing phosphate, improved rate performance can be obtained, while reducing the dissolution of the Mn element, obtaining improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material are also improved.

[0037] In any embodiment, A 2 The alloy may include any one element selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W, and may optionally include any one element selected from the group consisting of Mg and Nb.

[0038] In any embodiment, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may optionally include at least two elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may further optionally include at least two elements selected from Ti, V, Co and Mg, and may further optionally include at least two elements selected from Ti, V, Co and Mg, and may further optionally include more than one element selected from Ti, V, Co and Mg.

[0039] In any embodiment, C 2 Includes any one element selected from B, S, Si and N, and S is optional.

[0040] In any embodiment, D 2 The element comprises any one element selected from S, F, Cl and Br, and F is optional.

[0041] In any embodiment, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is selected from 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0. 75, x1 is selected from the range of 0.001 to 0.1, z1 is selected from the range of 0.001 to 0.5, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9 range, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is selected from the range of 0.001 to 0.5, and n1 is selected from the range of 0.001 to 0.1.

[0042] By doping a specific element in a specific amount at the transition metal position of the lithium-containing phosphate and optionally at the Li position, P position and / or O position, especially doping a specific element in a specific amount at the transition metal position and P position of the lithium-containing phosphate or at the Li position, transition metal position, P position and O position of the lithium-containing phosphate, it is possible to improve the rate performance, reduce the dissolution of the Mn element, improve the cycle performance and / or high temperature stability, and increase the gram capacity and compaction density of the second positive electrode active material.

[0043] In any embodiment, z1:n1 is selected from the range of 0.002 to 500, and can be selected from the range of 0.2 to 100, and can be selected from the range of 0.2 to 50. Thus, the defects of the second positive electrode active material can be further reduced, the integrity of the framework structure of the second positive electrode active material can be further improved, the structural stability of the second positive electrode active material can be effectively improved, and the cycle stability of the battery can be improved.

[0044] In any embodiment, A 2 comprising one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; B 2 Includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge; C 2 including one or more elements selected from B, S, Si and N; D 2 It includes one or more elements selected from S, F, Cl and Br; m1 is selected from the range of 0.9 to 1.1, x1 is selected from the range of 0.001 to 0.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is selected from the range of 0.001 to 0.1.

[0045] By doping specific elements in specific amounts at the Li position, transition metal position, P position and O position of the lithium-containing phosphate at the same time, improved rate performance can be obtained, while reducing the dissolution of the Mn element, obtaining improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the second positive electrode active material can also be improved.

[0046] In any embodiment, B 2 It includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and may optionally include one or more elements selected from Zn, Ti, V, Co and Mg; C 2 It includes one or more elements selected from B, Si, N and S; m1 is selected from the range of 0.9 to 1.1, x1 is 0, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is 0.

[0047] By doping specific elements in specific amounts at both the transition metal site and the P site of the lithium-containing phosphate, the rate performance can be improved, the dissolution of the Mn element can be reduced, the cycle performance and / or high temperature stability can be improved, and the gram capacity and compaction density of the second positive electrode active material can be increased.

[0048] In any embodiment, a1:x1 is in the range of 1 to 1200, optionally in the range of 9 to 1100, and more optionally in the range of 190-998.

[0049] In any embodiment, z1:(1-z1) is 1:9 to 1:999, and can be optionally 1:499 to 1:249.

[0050] When the above conditions are met, the energy density and cycle performance of the second positive electrode active material can be further improved.

[0051] In any embodiment, the second positive electrode active material includes a second core and a second shell covering the second core, the second core includes the compound represented by formula (II); the second shell includes one or more coating layers; each coating layer has ionic conductivity and / or electronic conductivity. By arranging a coating layer having ionic conductivity and / or electronic conductivity on the surface of the second core, a second positive electrode active material having a core-shell structure is provided, and the second positive electrode active material is applied to a battery to improve the high temperature cycle performance, cycle stability and high temperature storage performance of the battery.

[0052] In any embodiment, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

[0053] In any embodiment, the second shell includes a coating layer; optionally, the coating layer includes one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer. The above materials can be used to obtain a coating layer with ionic conductivity and / or electronic conductivity, thereby improving the high temperature cycle performance, cycle stability and high temperature storage performance of the battery.

[0054] In any embodiment, the second shell includes a first coating layer covering the second core and a second coating layer covering the first coating layer; optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer; more optionally, the first coating layer includes one or more selected from pyrophosphate, phosphate, oxide and boride, and the second coating layer includes one or more selected from carbon and doped carbon. The use of a first coating layer of a specific material and a second coating layer of a specific material can further improve the rate performance and further reduce the dissolution of the Mn element, thereby improving the cycle performance and / or high temperature stability of the battery.

[0055] In any embodiment, the second shell includes a first coating layer covering the second core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; optionally, the first coating layer, the second coating layer, and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride, and polymer; more optionally, the first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphate, oxide, and boride, and the third coating layer includes one or more selected from carbon and doped carbon. The use of a first coating layer of a specific material, a second coating layer of a specific material, and a third coating layer of a specific material further improves the rate performance, further reduces the dissolution of the Mn element, thereby improving the cycle performance and / or high temperature stability of the battery, and further increases the gram capacity and compaction density of the second positive electrode active material.

[0056] In any embodiment, the pyrophosphate is M i (P2O7) j and / or,

[0057] The phosphate is X p (PO4) q and / or,

[0058] The doping element in the doped carbon includes one or more elements selected from Group IIIA, Group VA, Group VIA and Group VIIA; and / or,

[0059] The oxide is M' k O l and / or,

[0060] The boride is Z v B w and / or,

[0061] The polymer includes one or more selected from polysaccharides and their derivatives, and polysiloxanes;

[0062] M, X and Z each independently include one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII;

[0063] i is selected from the range of 1 to 4;

[0064] j is selected from the range of 1 to 6;

[0065] p is selected from the range of 1 to 2;

[0066] q is selected from the range of 1 to 4;

[0067] M′ comprises one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb;

[0068] k is greater than 0 and less than or equal to 2;

[0069] l is greater than 0 and less than or equal to 5;

[0070] v is selected from the range of 1 to 7;

[0071] w is selected from the range of 1 to 2.

[0072] By using the above materials as the coating layer, the dissolution of the Mn element can be further reduced, the gram capacity and compaction density of the second positive electrode active material can be further increased, and the rate performance, high-temperature cycle performance and high-temperature storage performance of the battery can be further improved.

[0073] In any embodiment, M, X and Z each independently include one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, Mn and Al; and / or,

[0074] The doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; and / or,

[0075] M′ comprises one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Co, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and may optionally comprise one or more elements selected from Mg, Al, Si, Zn, Zr and Sn; and / or

[0076] The polysiloxane is selected from one or more of linear polysiloxane and cyclic polysiloxane; and / or,

[0077] The polysaccharide is selected from one or more of plant polysaccharides and marine polysaccharides.

[0078] By using the above-mentioned specific material as the coating layer, the dissolution of the Mn element can be further reduced, and the high-temperature cycle performance and high-temperature storage performance of the battery can be further improved.

[0079] In any embodiment, the second positive electrode active material includes a second core and a second shell covering the second core, wherein the second core includes Li m1 Mn 1-y1-y2 Fe y2 B 2 y1 P1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 The invention comprises one or more elements selected from B, S, Si and N; the second shell comprises a first coating layer covering the second core and a second coating layer covering the first coating layer, the first coating layer comprises pyrophosphate MP2O7 and phosphate XPO4, M and X each independently comprise one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; the second coating layer comprises carbon. By performing specific element doping and surface coating on the lithium-containing phosphate, the dissolution of the Mn element in the lithium insertion process can be effectively reduced, and the migration of lithium ions can be promoted, thereby improving the rate performance of the battery, and improving the cycle performance and high temperature performance of the battery.

[0080] In any embodiment, the second positive electrode active material includes a second core and a second shell covering the second core, wherein the second core includes Li m1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 The second shell comprises a first coating layer covering the second core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the first coating layer comprises pyrophosphate Li r QP2O7 and / or Q s (P2O7) t , 0≤r≤2, 1≤s≤4, 1≤t≤6, the pyrophosphate Li r QP2O7 and / or Q s (P2O7) tThe Q in each independently comprises one or more elements selected from Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; the second coating layer comprises crystalline phosphate XPO4, and X comprises one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; the third coating layer comprises carbon. Thus, the second positive electrode active material can improve the gram capacity and cycle performance of the battery.

[0081] In any embodiment, the one or more coating layers in the second shell that are farthest from the second core each independently include one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives. Thus, the uniformity of the coating can be improved, and the interface side reactions caused by high voltage can be effectively blocked, thereby improving the high-temperature cycle performance and high-temperature storage performance of the second positive electrode active material; and the coating layer has good ionic conductivity, which helps to improve the gram capacity of the second positive electrode active material and reduce the heat generation of the battery.

[0082] In any embodiment, the polysiloxane comprises a structural unit represented by formula (i).

[0083]

[0084] R1 and R2 are independently selected from H, -COOH, -OH, -SH, -CN, -SCN, amino, phosphate, carboxylate, amide, aldehyde, sulfonyl, polyether segment, C1-C20 aliphatic, C1-C20 halogenated aliphatic, C1-C20 heteroaliphatic, C1-C20 halogenated heteroaliphatic, C6-C20 aromatic, C6-C20 halogenated aromatic, C2-C20 heteroaromatic and C2-C20 halogenated heteroaromatic; optionally, R1 and R2 are independently selected from H, amino, phosphate, polyether segment, C1-C8 alkyl, C1-C8 halogenated alkyl, C1-C8 heteroalkyl, C1-C8 halogenated heteroalkyl, C2-C8 alkenyl and C2-C8 halogenated alkenyl.

[0085] In any embodiment, the polysiloxane further comprises an end-capping group, which includes one or more of the following functional groups: polyether, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl, C2-C8 haloalkenyl, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy, C2-C8 epoxy, hydroxyl, C1-C8 hydroxyalkyl, amino, C1-C8 aminoalkyl, carboxyl, C1-C8 carboxylalkyl.

[0086] In any embodiment, the polysiloxane includes polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl functionalized polysiloxane, epoxy-terminated polysiloxane, methoxy-terminated polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, polymethylchloropropylsiloxane, hydroxy-terminated polydimethylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, aminoethylaminopropyl polydimethylsiloxane, terminal polyether polydimethylsiloxane, side chain aminopropyl polysiloxane. , aminopropyl-terminated polydimethylsiloxane, side chain phosphate grafted polydimethylsiloxane, side chain polyether grafted polydimethylsiloxane, 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, cyclic polymethylvinylsiloxane, hexadecylcyclooctasiloxane, tetradecamethylcycloheptasiloxane, cyclic polydimethylsiloxane or more.

[0087] In any embodiment, the number average molecular weight of the polysiloxane, the polysaccharide and the polysaccharide derivative is independently below 300,000, optionally 10,000 to 200,000, more optionally 20,000 to 120,000, further optionally 400 to 80,000.

[0088] In any embodiment, the mass percentage of polar functional groups in the polysiloxane is α, 0≤α<50%, optionally, 5%≤α≤30%.

[0089] In any embodiment, the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH and its salts, -R-OH, -SO3H and its salts, -R-OH, -R-SO3H and its salts, sulfate, alkoxy, R represents an alkylene group, optionally representing a C1-C5 alkylene group; optionally, the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH, -COOLi, -COONa, -COOK, -SO3H, -SO3Li, -SO3Na, -SO3K, -CH2-SO3H, -CH2-SO3Li, -CH2-SO3Na, -CH2-SO3K, methoxy, ethoxy.

[0090] In any embodiment, the polysaccharide includes one or more selected from pectin, carboxymethyl starch, hydroxypropyl starch, dextrin, cellulose ether, carboxymethyl chitosan, hydroxyethyl cellulose, carboxymethyl cellulose, carboxypropyl methyl cellulose, guar gum, sesbania gum, gum arabic, lithium alginate, sodium alginate, potassium alginate, fucoidan, agar, carrageenan, carrageenan, xanthan gum and fenugreek gum.

[0091] In any embodiment, the mass percentage of the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivative is independently 20% to 85%, optionally 30% to 78%.

[0092] In any embodiment, the lattice mismatch between the material of the second core and the material of the second shell is less than 10%, thereby enabling good contact between the second core and the second shell (or coating layer) to prevent the second shell (or coating layer) from falling off.

[0093] In any embodiment, based on the total weight of the second positive electrode active material, the manganese content is in the range of 10-35 wt %, optionally in the range of 13.3-33.2 wt %, more optionally in the range of 15-30 wt %, and further optionally in the range of 17-20 wt %.

[0094] In any embodiment, the content of phosphorus is in the range of 12-25 weight %, optionally in the range of 15-20 weight %, and more optionally in the range of 16.8-19.5 weight %.

[0095] In any embodiment, the weight ratio of manganese element to phosphorus element is in the range of 0.71-1.85, optionally 0.90-1.25, and more preferably 0.95-1.20.

[0096] Limiting the content of manganese within the above range can further improve the stability and density of the second positive electrode active material, thereby improving the battery's cycling, storage and compaction properties; and can maintain a higher voltage platform, thereby improving the battery's energy density.

[0097] Limiting the content of phosphorus within the above range can effectively reduce the influence of small polaron conductivity on the conductivity of the second positive electrode active material, and can further improve the stability of the lattice structure, thereby improving the overall stability of the second positive electrode active material.

[0098] Limiting the weight ratio of manganese to phosphorus within the above range can further reduce manganese dissolution, improve the stability and gram capacity of the second positive electrode active material, and improve the cycle performance and storage performance of the battery; it can also reduce impurities, enable the second positive electrode active material to maintain a higher discharge voltage platform, and enable the battery to have a high energy density.

[0099] In any embodiment, the surface of the second positive electrode active material is coated with one or more of carbon and doped carbon; optionally, the surface of the second positive electrode active material is coated with carbon, thereby improving the conductivity of the second positive electrode active material.

[0100] In any embodiment, the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine.

[0101] In any embodiment, the coating amount of the second shell is 0.1-6% by weight, based on the weight of the second core. The coating amount of the coating layer is preferably within the above range, which can fully coat the second core and further improve the kinetic performance of the battery without sacrificing the gram capacity of the second positive electrode active material.

[0102] In any embodiment, the coating amount of the first coating layer is greater than 0 and less than or equal to 7% by weight, optionally greater than 0 and less than or equal to 6% by weight, more optionally greater than 0 and less than or equal to 5.5% by weight or 4-5.6% by weight, and further optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the second core; and / or, the coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, more optionally 2-4% by weight or 3-5% by weight, based on the weight of the second core; and / or, the coating amount of the third coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the second core.

[0103] In any embodiment, the second shell further includes a fourth coating layer coating the third coating layer and a fifth coating layer coating the fourth coating layer; the coating amounts of the fourth coating layer and the fifth coating layer are each independently 0.01-10% by weight, optionally 0.05-10% by weight, more optionally 0.1-5% by weight, and further 0.1-2% by weight, based on the weight of the second core.

[0104] In any embodiment, the second shell is located on 40% to 90% of the surface of the second core, and optionally 60% to 80% of the surface, so that the second core can be fully coated, thereby improving the dynamic performance of the battery.

[0105] In any embodiment, the second shell has a thickness of 1-15 nm.

[0106] In any embodiment, the thickness of the first coating layer is 1-10nm, optionally 2-10nm; and / or the thickness of the second coating layer is 2-25nm, optionally 2-15nm, and more optionally 3-15nm; and / or the thickness of the third coating layer is 2-25nm, optionally 5-25nm.

[0107] In any embodiment, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate and oxide, and one or more selected from the pyrophosphate, phosphate and oxide are crystalline; optionally, the crystallinity of the pyrophosphate, the phosphate and the oxide is each independently 10% to 100%, and more optionally 50% to 100%.

[0108] Pyrophosphates and phosphates with a certain degree of crystallinity are not only conducive to fully utilizing the pyrophosphate coating to reduce manganese dissolution and the phosphate coating's excellent ability to conduct lithium ions and reduce interface side reactions, but also enable the pyrophosphate coating and the phosphate coating to better lattice match, thereby achieving a close bond between the coatings.

[0109] In any embodiment, in the second shell, the weight ratio of pyrophosphate to phosphate and the weight ratio of pyrophosphate to oxide are independently 1:3 to 3:1, and can be 1:3 to 1:1. Thus, by having pyrophosphate and phosphate in a suitable weight ratio range or pyrophosphate and oxide in a suitable weight ratio range, manganese dissolution can be effectively reduced, surface impurity lithium content can be effectively reduced, and interface side reactions can be reduced, thereby improving the high temperature storage performance and high temperature cycle performance of the battery.

[0110] In any embodiment, the one or more coating layers independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon; optionally, in the carbon, the molar ratio of the SP2 carbon to the SP3 carbon is any value in the range of 0.07-13, more preferably any value in the range of 0.1-10, and further preferably any value in the range of 2.0-3.0. By selecting the form of carbon in the carbon coating layer, the comprehensive electrical performance of the battery is improved.

[0111] In any embodiment, the one or more coating layers independently include doped carbon, and the mass content of the doping element in the doped carbon is less than 30%; optionally, the mass content of the doping element in the doped carbon is less than 20%. The doping elements within the above content range can not only fully improve the conductivity of the pure carbon layer, but also effectively avoid excessive surface activity caused by excessive doping of the doping elements, thereby effectively controlling the interface side reactions caused by excessive doping of the coating layer.

[0112] In any embodiment, the one or more coating layers independently include doped carbon, in which the doping element is nitrogen and / or sulfur, and the mass content of the doping element in the doped carbon is 1% to 15%; or, the doping element is phosphorus, boron and / or fluorine, and the mass content of the doping element in the doped carbon is 0.5% to 5%. Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.

[0113] In any embodiment, the one or more coating layers independently include pyrophosphate, the pyrophosphate has a lattice spacing range of 0.293-0.470nm, optionally 0.297-0.462nm or 0.293-0.326nm, and more optionally 0.300-0.310nm, and a crystal orientation (111) angle range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°.

[0114] In any embodiment, the one or more coating layers independently include phosphate, the phosphate has a lattice spacing range of 0.244-0.425nm, optionally 0.345-0.358nm, and a crystal orientation (111) angle range of 20.00°-37.00°, optionally 24.25°-26.45°.

[0115] In any embodiment, the first coating layer or the second coating layer comprises a phosphate.

[0116] As a result, the impurity phase in the coating layer can be effectively reduced, thereby improving the material's gram capacity, cycle performance and rate performance.

[0117] In any embodiment, the lattice change rate of the second positive electrode active material before and after complete lithium deintercalation is 50% or less, optionally 9.8% or less, more optionally 8.1% or less, further optionally 7.5% or less, further optionally 6% or less, further optionally 4% or less, further optionally 3.8% or less, further optionally 2.0%-3.8%, thereby improving the rate performance of the battery.

[0118] In any embodiment, the Li / Mn antisite defect concentration of the second positive electrode active material is 5.3% or less, optionally 5.1% or less, more optionally 4% or less, further optionally 2.2% or less, further optionally 2% or less, further optionally 1.5%-2.2% or 0.5% or less. By reducing the Li / Mn antisite defect concentration, it is beneficial to improve the gram capacity and rate performance of the second positive electrode active material.

[0119] In any embodiment, the surface oxygen valence state of the second positive electrode active material is below -1.55, optionally below -1.82, more optionally below -1.88, further optionally below -1.90 or -1.98 to -1.88, further optionally -1.98 to -1.89, further optionally -1.98 to -1.90. By reducing the surface oxygen valence state, the interface side reaction between the second positive electrode active material and the electrolyte can be reduced, thereby improving the cycle performance and high temperature stability of the battery.

[0120] In any embodiment, the battery cell further includes a negative electrode plate and a separator.

[0121] A second aspect of the present application provides a battery, comprising the battery cell of the first aspect of the present application.

[0122] A third aspect of the present application provides an electrical device, comprising the battery of the second aspect of the present application.

[0123] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0124] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0125] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0126] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0127] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0128] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0129] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0130] Figure 6 It is a schematic diagram of an embodiment of an electrical device including the battery of the present application as a power source.

[0131] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0132] Hereinafter, the battery cells, batteries and electrical devices of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0133] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0134] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0135] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0136] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0137] If not otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0138] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0139] In various places of this specification, the substituents of the compounds are disclosed in groups or ranges. It is explicitly expected that this description includes each individual subcombination of the members of these groups and ranges. For example, it is explicitly expected that the term "C1-C6 alkyl" discloses C1, C2, C3, C4, C5, C6, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C6, C2-C5, C2-C4, C2-C3, C3-C6, C3-C5, C3-C4, C4-C6, C4-C5, C5-C6 alkyl individually.

[0140] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0141] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0142] Unless otherwise specified, the ratio parameters involved in this application are compared in the same unit. For example, the ratio of the mass of A to that of B is 1:1, and the units of the mass of A and B are the same.

[0143] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0144] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0145] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0146] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0147] A battery cell generally includes an electrode assembly. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0148] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0149] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to needs.

[0150] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0151] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0152] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0153] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0154] The battery cell provided in the embodiment of the present application includes a positive electrode plate and an electrolyte, and the battery cell also includes a negative electrode plate and a separator.

[0155] The positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material and the second positive electrode active material can extract and embed lithium ions, the first positive electrode active material includes Ni element, the second positive electrode active material includes Fe element, the first positive electrode active material and the second positive electrode active material have different crystal forms, and the specific surface area of ​​the first positive electrode active material is smaller than the specific surface area of ​​the second positive electrode active material.

[0156] The electrolyte solution includes a non-aqueous solvent, an electrolyte salt, and a first additive, wherein the electrolyte salt includes a first cation and a first anion, the first additive includes a second cation and a second anion, and the second anion includes HPO4 2- 、H2PO4 - One or both of the following.

[0157] The weight content of the first anion in the electrolyte is recorded as w a The weight content of the second anion in the electrolyte is recorded as w b, all based on the total weight of the electrolyte. Based on the total weight of the positive electrode active material, the weight content of the first positive electrode active material is recorded as w1, and the weight content of the second positive electrode active material is recorded as w2. The battery cell satisfies 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0.

[0158] Combining different crystal forms of positive electrode active materials can help improve the overall performance of the battery. However, when different crystal forms of positive electrode active materials are used in combination, the internal resistance of the battery will continue to increase during the cycle. In particular, the internal resistance of the battery is larger in the later stage of use, resulting in a more obvious attenuation of the battery cycle performance. For example, when the battery is used in an electric vehicle, the power attenuation of the electric vehicle is larger, resulting in a poor driving experience for the driver.

[0159] The specific surface area of ​​the first positive electrode active material provided in the embodiment of the present application is smaller than the specific surface area of ​​the second positive electrode active material, so that the second positive electrode active material is generally easier to absorb water, so that its moisture content is higher, which in turn leads to a higher moisture content in the electrolyte. When the moisture content in the electrolyte is high, the moisture will react with the electrolyte salt and produce HF, and HF will form hydrofluoric acid when dissolved in water. Hydrofluoric acid will destroy the structure of the positive electrode active material, especially the surface structure of the first positive electrode active material, thereby causing the internal resistance to continue to increase during the battery cycle. In particular, the internal resistance of the battery is larger in the later stage of use, resulting in a more obvious attenuation of the battery cycle performance.

[0160] The second anion includes HPO4 2- 、H2PO4 - One or two of the above, and the second anion is amphiphilic, which can neutralize the hydrofluoric acid in the electrolyte and reduce the acidity of the electrolyte, thereby reducing the damage of hydrofluoric acid to the structure of the positive electrode active material, especially the surface structure of the first positive electrode active material, and thus reducing the internal resistance growth rate during the battery cycle. However, when the content of the first anion is too high, it will participate in the formation of the solid electrolyte interface film (hereinafter referred to as SEI film) on the surface of the negative electrode, thereby causing the stability of the SEI film, especially the high temperature stability, to deteriorate, thereby increasing the irreversible capacity of the battery on the one hand, and increasing the internal resistance growth rate during the battery cycle on the other hand.

[0161] w1 is the weight content of the first positive electrode active material in the positive electrode active material of the positive electrode sheet, and w2 is the weight content w2 of the second positive electrode active material in the positive electrode active material of the positive electrode sheet, so that w1 / w2 can reflect the relative content of the first positive electrode active material and the second positive electrode active material in the positive electrode active material. When the relative content of the second positive electrode active material in the positive electrode active material decreases, the moisture content of the positive electrode active material decreases; when the relative content of the second positive electrode active material in the positive electrode active material increases, the moisture content of the positive electrode active material increases.

[0162] w a is the weight content of the first anion in the electrolyte, w b is the weight content of the second anion in the electrolyte, and thus w b / (w a +w b ) can reflect the relative content of the second anion in the electrolyte anion. When the relative content of the second anion in the electrolyte anion is high, the second anion will not only neutralize the hydrofluoric acid in the electrolyte and reduce the acidity of the electrolyte, but also participate in the formation of the SEI film, which will lead to the stability of the SEI film, especially the high-temperature stability, which will increase the irreversible capacity of the battery on the one hand, and increase the internal resistance growth rate during the battery cycle on the other hand.

[0163] By adjusting the weight content of the first anion in the electrolyte w a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, the amount of the second anion can be better matched with the amount of the first positive electrode active material and the second positive electrode active material, thereby reducing the internal resistance growth rate during the battery cycle, reducing the acidity of the electrolyte, and making the battery have good cycle performance.

[0164] In some embodiments, 1.17≤100×(w1 / w2)×[w b / (w a +w b )]≤16.33, optionally, 2.00≤100×(w1 / w2)×[w b / (w a +w b )]≤11.67,2.00≤100×(w1 / w2)×[w b / (w a +wb )]≤8.17.

[0165] By further adjusting the weight content of the first anion in the electrolyte w a , the weight content of the second anion in the electrolyte w b The relationship between the weight content w1 of the first positive electrode active material in the positive electrode active material and the weight content w2 of the second positive electrode active material in the positive electrode active material can better match the amount of the second anion with the amount of the first positive electrode active material and the second positive electrode active material, thereby further reducing the internal resistance growth rate and the acidity of the electrolyte during the battery cycle, so that the battery has better cycle performance.

[0166] In some embodiments, the weight content w1 of the first positive electrode active material may be 33.5%-95%, and the weight content w2 of the second positive electrode active material may be 5%-66.5%. Alternatively, the weight content w1 of the first positive electrode active material may be 50%-70%, and the weight content w2 of the second positive electrode active material may be 30%-50%.

[0167] In some embodiments, w1 / w2 may be 0.50-19.0, and may optionally be 1.00-2.33.

[0168] By adjusting the weight content w1 of the first positive electrode active material and / or the weight content w2 of the second positive electrode active material within the above range, the battery can have both high energy density and long cycle life.

[0169] In some embodiments, the weight content of Ni in the positive electrode film is recorded as w Ni , based on the total weight of the positive electrode film layer, 10.2% ≤ w Ni ≤28.8%, optionally, 15.1%≤w Ni ≤21.2%.

[0170] In some embodiments, the weight content of Fe element in the positive electrode film layer is recorded as w Fe , based on the total weight of the positive electrode film layer, 1.2% ≤ w Fe ≤11.1%, optionally, 3.9%≤w Fe ≤8.7%.

[0171] By adjusting the weight content of the Ni element and / or the Fe element within the above range, the battery can have both high energy density and long cycle life.

[0172] In some embodiments, the specific surface area of ​​the first positive electrode active material may be 0.5-1 m 2 / g, optional 0.6-0.9m 2 / g.

[0173] In some embodiments, the specific surface area of ​​the second positive electrode active material may be 11-18.4 m 2 / g, optional 11.9-15.0m 2 / g.

[0174] When the specific surface area of ​​the second positive electrode active material is within the above range, it is beneficial for the battery to have a lower internal resistance growth rate and a longer cycle life.

[0175] The specific surface area of ​​a material (such as a first positive electrode active material, a second positive electrode active material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested with reference to GB / T 19587-2017 using a nitrogen adsorption specific surface area analysis test method and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be a Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA. Before the test, the material powder can be placed in a vacuum oven and dried at 200°C for more than 2 hours, and the sampling mass of the material powder can be more than 20g.

[0176] In some embodiments, 0.5%≤w b / (w a +w b )≤5.5%, optionally, 1.5%≤w b / (w a +w b )≤4.5%. b / (w a +w b ) is within the above range, it is beneficial for the battery to have a lower internal resistance growth rate and a longer cycle life.

[0177] In some embodiments, the first cation includes a lithium ion.

[0178] In some embodiments, the first cation may include lithium ions and Me ions at the same time, and the Me ions include one or more of sodium ions, potassium ions, calcium ions, and magnesium ions.

[0179] In some embodiments, the second cation may include one or more of lithium ions and Me ions, and the Me ions may include one or more of sodium ions, potassium ions, calcium ions, and magnesium ions.

[0180] In some embodiments, the first anion may include, but is not limited to, PF6 - 、ClO4 - 、AsF6 - 、BF4 - 、N(CF3SO2)2- (TFSI - ), CF3SO3 - 、N(FSO2)2 - (FSI - )、C(SO2CF3)3 - PO2F2 - , difluorooxalate borate ion (DFOB - ), borate oxalate ion (BOB - ), difluorobis(oxalate)phosphate ion (DFOP - ), tetrafluorooxalate phosphate ion (TFOP - )

[0181] In some embodiments, the molar concentration of the first anion in the electrolyte may be 0.8-2 mol / L.

[0182] In some embodiments, the non-aqueous solvent may include, but is not limited to, one or more of cyclic carbonates, linear carbonates, and carboxylates. As an example, the non-aqueous solvent may include, but is not limited to, one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0183] In some embodiments, the electrolyte may further optionally include other additives. As an example, the other additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature or low temperature performance, etc., which are not limited in the embodiments of the present application.

[0184] The electrolyte can be prepared according to conventional methods in the art. For example, the non-aqueous solvent, the electrolyte salt (including the first cation and the first anion), the first additive (including the second cation and the second anion) and other components can be mixed evenly to obtain the electrolyte. There is no particular restriction on the order of adding the materials. For example, the electrolyte salt, the first additive and other components can be added to the non-aqueous solvent and mixed evenly to obtain the electrolyte.

[0185] The components and their contents in the electrolyte can be measured by methods known in the art, for example, by gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0186] In some embodiments, the ion content and compound content of the first anion and the second anion in the electrolyte can be quantitatively tested by an ion chromatograph, and w can be calculated. a 、w b and w b / (w a +w b ). For test standards, please refer to GB / T36240-2018.

[0187] The different crystal forms of the first positive electrode active material and the second positive electrode active material mean that the first positive electrode active material and the second positive electrode active material have different crystal systems.

[0188] In some embodiments, the first positive electrode active material may include a lithium-containing layered oxide, and the second positive electrode active material may include a lithium-containing phosphate.

[0189] The second positive electrode active material includes a lithium-containing phosphate, which has a one-dimensional ion transport channel and is generally an olivine structure. The second positive electrode active material has high stability and generally low production cost, which can reduce the cost of the battery and facilitate large-scale production. However, the compaction density of the second positive electrode active material is generally small, which is not conducive to the battery having a high energy density. The first positive electrode active material includes a lithium-containing layered oxide, which has a two-dimensional ion transport channel and also has a high gram capacity and a high voltage platform, which is conducive to the battery having a high energy density.

[0190] In addition, the second positive electrode active material usually has a larger specific surface area and is more susceptible to water absorption, which results in a higher moisture content, and in turn, a higher moisture content in the electrolyte. When the moisture content in the electrolyte is high, the moisture reacts with the electrolyte salt and produces HF, which dissolves in water to form hydrofluoric acid. Hydrofluoric acid destroys the structure of the positive electrode active material, especially the surface structure of the first positive electrode active material, resulting in a continuous increase in internal resistance during the battery cycle.

[0191] Therefore, the combination of the first positive electrode active material and the second positive electrode active material is conducive to obtaining a low-cost and high-energy-density battery. a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b)]≤19.0, and the amount of the second anion can be better matched with the amount of the first positive electrode active material and the second positive electrode active material, thereby reducing the internal resistance growth rate during the battery cycle and the acidity of the electrolyte, so that the battery has good cycle performance.

[0192] The first positive electrode active material and the second positive electrode active material may have regular morphology, such as spherical or quasi-spherical, or may have irregular morphology.

[0193] [First positive electrode active material]

[0194] In some embodiments, the first positive active material may include a compound represented by formula (I).

[0195] Li a A 1 b Ni c Co d B 1 e C 1 f O g D 1 h (I)

[0196] A 1 Includes one or more elements selected from Group IA, Group IIA, Group VIII, Group VIB, and Group IIB; B 1 including Mn and / or Al; C 1 comprising one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB, and Group VIII; D 1 It includes one or more elements selected from Group VIA and Group VIIA; a is selected from the range of 0.75 to 1.2; b is selected from the range of 0 to 0.2; c is selected from the range of 0.500 to 0.990; d is selected from the range of 0 to 0.490; e is selected from the range of 0.001 to 0.490; f is selected from the range of 0 to 0.1; g is selected from the range of 1.0 to 2.0; h is selected from the range of 0 to 1.0.

[0197] c is selected from the range of 0.500 to 0.990. When the content of Ni in the first positive electrode active material is high, its gram capacity is higher; however, at this time, the stability of the surface structure of the first positive electrode active material itself is poor, and by making the electrolyte contain an appropriate content of the second anion and adjusting 100×(w1 / w2)×[w b / (w a +w b)] Within a suitable range, the battery's cycle internal resistance growth rate can be reduced, the battery's cycle performance can be improved, and the battery can also have a high energy density.

[0198] Unless otherwise specified, in the above chemical formulas, when A 1 When there are two or more elements, the above-mentioned limitation on the numerical range of b is not only applicable to each element as A 1 The stoichiometric number of the element is also limited to each element as A 1 The sum of the stoichiometric numbers of the elements is limited. For example, when A 1 Two or more elements A 1 1. A 1 2……A 1 When n, A 1 1. A 1 2……A 1 Each of the stoichiometric numbers of n, b1, b2, ..., bn, must fall within the numerical range specified for b in the present application, and the sum of b1, b2, ..., bn must also fall within the numerical range.

[0199] Similarly, for B mentioned in the embodiments of this application 1 , C 1 , D 1 , A 2 , B 2 , C 2 , D 2 When M, M′, X, Z, P, Q, etc. are two or more elements, the numerical range of their stoichiometric numbers in the present application also has a similar meaning as above.

[0200] In some embodiments, c+d+e+f=1.

[0201] In some embodiments, g+h=2.

[0202] In some embodiments, A 1 It includes one or more elements selected from Na, K, Mg, Rb, Zn and Zr.

[0203] In some embodiments, C 1 It includes one or more elements selected from Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Cu, Ba, Mo, V, Ce, Nb, Sb, Ta, Ge, Nb, Sc, Ba, B, S and Y, and can be selected from one or more elements selected from Mg, Ti, W, Zr, Cr, Zn, Cu, V, Nb, Sr, Sb, Y

[0204] In some embodiments, D 1The invention comprises one or more elements selected from N, S, F, Cl and Br, and may optionally comprise S and / or F.

[0205] In some embodiments, a is selected from the range of 0.9 to 1.1.

[0206] In some embodiments, b is selected from the range of 0 to 0.1.

[0207] In some embodiments, c is selected from the range of 0.500 to 0.800, and optionally is selected from the range of 0.500 to 0.600.

[0208] In some embodiments, d is selected from the range of 0 to 0.320, and may optionally be selected from the range of 0 to 0.100.

[0209] When the content of Co in the first positive electrode active material is low, the material cost can be reduced; however, at this time, the stability of the surface structure of the first positive electrode active material itself is poor. By making the electrolyte contain an appropriate content of the second anion and adjusting 100×(w1 / w2)×[w b / (w a +w b )] Within a suitable range, the battery's cycle internal resistance growth rate can be reduced, the acidity of the electrolyte can be reduced, the battery's cycle performance can be improved, and the battery's manufacturing cost can be reduced.

[0210] In some embodiments, e is selected from the range of 0.100 to 0.450, and may be optionally selected from the range of 0.300 to 0.450.

[0211] In some embodiments, f is selected from the range of 0.001 to 0.1, and can be optionally selected from the range of 0.001 to 0.05.

[0212] In some embodiments, g is selected from the range of 1.9 to 2.0, and optionally selected from the range of 1.95 to 1.99.

[0213] In some embodiments, h is selected from the range of 0 to 0.1, and optionally from the range of 0.01 to 0.05.

[0214] In some embodiments, the first positive electrode active material may include a first core and a first shell covering the first core, wherein the first core includes the compound represented by the above formula (I); and the first shell includes one or more coating layers. Each coating layer has ionic conductivity and / or electronic conductivity.

[0215] In some embodiments, one or more coating layers in the first shell each independently include one or more selected from phosphate, pyrophosphate, carbon, doped carbon, oxide, and fast ion conductor, and may optionally include one or more selected from phosphate, pyrophosphate, and oxide.

[0216] In some embodiments, the first shell includes a coating layer; optionally, the coating layer includes one or more selected from phosphates, pyrophosphates, and oxides.

[0217] In some embodiments, the first shell includes a first coating layer coating the inner core and a second coating layer coating the first coating layer; optionally, the first coating layer and the second coating layer each independently include one or more selected from phosphates, pyrophosphates, and oxides; more optionally, the first coating layer includes one or more selected from phosphates and oxides, and the second coating layer includes one or more selected from pyrophosphates and oxides.

[0218] In some embodiments, the coating amount of the first shell may be 0.005-1 wt %, and optionally 0.01-0.5 wt %, based on the weight of the first core.

[0219] In some embodiments, the thickness of the first shell may be 2-200 nm, optionally 5-50 nm.

[0220] [Second positive electrode active material]

[0221] In some embodiments, the second positive electrode active material may include a compound represented by formula (II).

[0222] Li m1 A 2 x1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O 4-n1 D 2 n1 (II)

[0223] A 2 Includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB and Group VIB; B 2 Includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB, and Group VIII; C 2 Includes one or more elements selected from Group IIIA, Group IVA, Group VA and Group VIA; D 2It includes one or more elements selected from Group VIA and Group VIIA; m1 is selected from the range of 0.85 to 1.15; x1 is selected from the range of 0 to 0.1; y1 is selected from the range of 0 to 0.5; y2 is selected from the range of 0.1 to 1; 1-y1-y2 is selected from the range of 0 to 0.9; z1 is selected from the range of 0 to 0.5; n1 is selected from the range of 0 to 0.5.

[0224] A 2 , B 2 , C 2 and D 2 The elements doped at the Li position, transition metal position (such as Mn position and / or Fe position), P position and O position of the lithium-containing phosphate are respectively. Without wishing to be limited by theory, it is now believed that the performance improvement of the lithium-containing phosphate is related to reducing the lattice change rate of the lithium-containing phosphate during the lithium insertion and extraction process and reducing the surface activity. Reducing the lattice change rate can reduce the lattice constant difference between the two phases at the grain boundary, reduce the interfacial stress, and enhance the Li + The transmission capacity at the interface improves the rate performance of the second positive electrode active material. However, high surface activity can easily lead to serious side reactions at the interface, aggravating gas production, electrolyte consumption and interface damage, thereby affecting the battery's cycle performance. The lattice change rate can be reduced by doping with Li and / or transition metals. Transition metal doping can also effectively reduce surface activity, thereby reducing the dissolution of Mn elements and the side reactions at the interface between the second positive electrode active material and the electrolyte. P-site doping makes the change rate of the Mn-O bond length faster, reduces the migration barrier of the small polaron of the material, and is beneficial to improve the electronic conductivity. O-site doping has a good effect on reducing side reactions at the interface. P-site and / or O-site doping also affects the dissolution and kinetic properties of Mn elements with anti-site defects. Therefore, doping reduces the concentration of anti-site defects in the material, improves the kinetic properties and gram capacity of the material, and can also change the morphology of the particles, thereby improving the compaction density. By doping lithium-containing phosphates with specific elements in specific amounts at specific locations, improved rate performance can be obtained while reducing the dissolution of the Mn element, thereby improving cycle performance and / or high-temperature stability, and the gram capacity and compaction density of the material are also improved.

[0225] In some embodiments, A 2 It includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and can optionally include one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W.

[0226] In some embodiments, B 2It includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and can optionally include one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge.

[0227] In some embodiments, C 2 Includes one or more elements selected from B, S, Si and N.

[0228] In some embodiments, D 2 Includes one or more elements selected from S, F, Cl and Br.

[0229] In some embodiments, A 2 comprising any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally comprising any one element selected from Mg and Nb; and / or,

[0230] B 2 comprising one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally comprising at least two elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and more optionally comprising at least two elements selected from Ti, V, Co and Mg, and further optionally comprising at least two elements selected from Ti, V, Co and Mg, and further optionally comprising more than one element selected from Ti, V, Co and Mg; and / or,

[0231] C 2 comprising any one element selected from B, S, Si and N, optionally S; and / or,

[0232] D 2 The element comprises any one element selected from S, F, Cl and Br, and F is optional.

[0233] By selecting the Li-site doping element within the above range, the lattice change rate during the delithiation process can be further reduced, thereby further improving the rate performance of the battery.

[0234] By selecting the transition metal doping element within the above range, the electronic conductivity can be further improved and the lattice change rate can be further reduced, thereby improving the rate performance and gram capacity of the battery.

[0235] By selecting the P-site doping element within the above range, the rate performance of the battery can be further improved.

[0236] By selecting the O-position doping element within the above range, the side reactions at the interface can be further reduced and the high temperature performance of the battery can be improved.

[0237] In some embodiments, m1 is selected from the range of 0.9 to 1.1, and may be optionally selected from the range of 0.97 to 1.01.

[0238] In some embodiments, x1 is selected from the range of 0.001 to 0.1, and may be optionally selected from the range of 0.001 to 0.005.

[0239] In some embodiments, y1 is selected from the range of 0.001 to 0.5, and may be optionally selected from the range of 0.005 to 0.2.

[0240] In some embodiments, y2 is selected from the range of 0.2 to 0.9, and may be optionally selected from the range of 0.3 to 0.7.

[0241] In some embodiments, 1-y1-y2 is selected from the range of 0.05 to 0.75, and can be optionally selected from the range of 0.22 to 0.68.

[0242] In some embodiments, z1 is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.001 to 0.1, and more optionally selected from the range of 0.001 to 0.005.

[0243] In some embodiments, n1 is selected from the range of 0 to 0.1, and may be optionally selected from the range of 0.001 to 0.005.

[0244] By selecting the y1 value within the above range, the gram capacity and rate performance of the second positive electrode active material can be further improved.

[0245] By selecting the x1 value within the above range, the kinetic performance of the second positive electrode active material can be further improved.

[0246] By selecting the z1 value within the above range, the rate performance of the battery can be further improved.

[0247] By selecting the n1 value within the above range, the high temperature performance of the battery can be further improved.

[0248] In some embodiments, y1 is 0 and y2 is 1.

[0249] In some embodiments, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, and 1-y1-y2 is selected from the range of 0.05 to 0.75.

[0250] In some embodiments, y1 is selected from the range of 0.005 to 0.2, y2 is selected from the range of 0.3 to 0.7, and 1-y1-y2 is selected from the range of 0.22 to 0.68.

[0251] In some embodiments, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is 0.

[0252] In some embodiments, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is 0, and n1 is selected from the range of 0.001 to 0.1. , n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is selected from the range of 0.001 to 0.5, and n1 is 0.

[0253] Therefore, by doping a specific element in a specific amount at the transition metal position of the lithium-containing phosphate and optionally at the Li position, P position and / or O position, especially doping a specific element in a specific amount at the transition metal position and P position of the lithium-containing phosphate or at the Li position, transition metal position, P position and O position of the lithium-containing phosphate, the rate performance can be improved, the dissolution of the Mn element can be reduced, the cycle performance and / or high temperature stability can be improved, and the gram capacity and compaction density of the second positive electrode active material can be increased.

[0254] In some embodiments, z1:n1 can be selected from the range of 0.002 to 500, can be selected from the range of 0.2 to 100, and can be selected from the range of 0.2 to 50, such as 0.2, 0.8, 1, 1.25, 4, 5, 50, or a range consisting of any two of the above values. Thus, the defects of the second positive electrode active material can be further reduced, the integrity of the framework structure of the second positive electrode active material can be further improved, the structural stability of the second positive electrode active material can be effectively improved, and the cycle stability of the battery can be improved.

[0255] In some embodiments, a1:x1 may be in the range of 1 to 1200, optionally in the range of 9 to 1100, and more optionally in the range of 190 to 998. When the above conditions are met, the energy density and cycle performance of the second positive electrode active material may be further improved.

[0256] In some embodiments, z1:(1-z1) may be 1:9 to 1:999, and may be 1:499 to 1:249. When the above conditions are met, the energy density and cycle performance of the second positive electrode active material may be further improved.

[0257] In some embodiments, A 2 comprising one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; B 2 Includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge; C 2 including one or more elements selected from B, S, Si and N; D 2 It includes one or more elements selected from S, F, Cl and Br; m1 is selected from the range of 0.9 to 1.1, x1 is selected from the range of 0.001 to 0.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is selected from the range of 0.001 to 0.1.

[0258] By doping specific elements in specific amounts at the Li position, transition metal position, P position and O position of the lithium-containing phosphate at the same time, improved rate performance can be obtained, while reducing the dissolution of the Mn element, obtaining improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the second positive electrode active material can also be improved.

[0259] In some embodiments, B 2 It includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and may optionally include one or more elements selected from Zn, Ti, V, Co and Mg; C2 It includes one or more elements selected from B, Si, N and S; m1 is selected from the range of 0.9 to 1.1, x1 is 0, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is 0.

[0260] By doping specific elements in specific amounts at both the transition metal site and the P site of the lithium-containing phosphate, the rate performance can be improved, the dissolution of the Mn element can be reduced, the cycle performance and / or high temperature stability can be improved, and the gram capacity and compaction density of the second positive electrode active material can be increased.

[0261] In some embodiments, the second positive electrode active material includes a second core and a second shell coating the second core, wherein the second core includes the compound represented by the above formula (II). The second shell includes one or more coating layers. The coating layer has ionic conductivity and / or electronic conductivity. In practice, each coating layer may be completely coated or partially coated.

[0262] By arranging a coating layer with ionic conductivity and / or electronic conductivity on the surface of the second inner core, a second positive electrode active material with a core-shell structure is provided. Applying the second positive electrode active material to the battery can improve the high temperature cycle performance, cycle stability and high temperature storage performance of the battery.

[0263] In some embodiments, one or more coating layers each independently include one or more selected from the group consisting of pyrophosphate, phosphate, carbon, doped carbon, oxide, boride, and polymer.

[0264] In some embodiments, the second shell comprises a coating layer; optionally, the coating layer comprises one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

[0265] The above materials can be used to obtain a coating layer with ionic conductivity and / or electronic conductivity, thereby improving the high-temperature cycle performance, cycle stability and high-temperature storage performance of the battery.

[0266] In some embodiments, the second shell includes a first coating layer coating the second inner core and a second coating layer coating the first coating layer; optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

[0267] Using the above materials as the materials for the coating layer and providing two coating layers can further improve the high temperature cycle performance, cycle stability and high temperature storage performance of the battery.

[0268] In some embodiments, the first coating layer includes one or more selected from pyrophosphate, phosphate, oxide, and boride, and the second coating layer includes one or more selected from carbon and doped carbon.

[0269] The use of a first coating layer of a specific material and a second coating layer of a specific material can further improve the rate performance and further reduce the dissolution of the Mn element, thereby improving the cycle performance and / or high temperature stability of the battery.

[0270] In some embodiments, the second shell includes a first coating layer coating the second inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer; optionally, the first coating layer, the second coating layer and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

[0271] Using the above materials as the materials for the coating layer and providing three layers of coating layers can further reduce the dissolution of the Mn element and further improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the battery.

[0272] In some embodiments, the first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphates, oxides, and borides, and the third coating layer includes one or more selected from carbon and doped carbon.

[0273] The use of a first coating layer of a specific material, a second coating layer of a specific material, and a third coating layer of a specific material further improves the rate performance, further reduces the dissolution of the Mn element, thereby improving the cycle performance and / or high temperature stability of the battery, and further increases the gram capacity and compaction density of the second positive electrode active material.

[0274] In some embodiments, the pyrophosphate is i (P2O7) j M includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; i is selected from the range of 1 to 4, and j is selected from the range of 1 to 6.

[0275] In some embodiments, the phosphate is X p (PO4) q X includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; p is selected from the range of 1 to 2; and q is selected from the range of 1 to 4.

[0276] In some embodiments, the doping element in the doped carbon includes one or more selected from Group IIIA, Group VA, Group VIA, and Group VIIA.

[0277] In some embodiments, the oxide is M' k O l M′ includes one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanide elements, and Sb; k is greater than 0 and less than or equal to 2; l is greater than 0 and less than or equal to 5.

[0278] In some embodiments, the boride is Z v B w Z includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; v is selected from the range of 1 to 7, and w is selected from the range of 1 to 2.

[0279] In some embodiments, the polymer includes one or more selected from polysaccharides and their derivatives, and polysiloxanes.

[0280] By using the above materials as the coating layer, the dissolution of the Mn element can be further reduced, the gram capacity and compaction density of the second positive electrode active material can be further increased, and the rate performance, high-temperature cycle performance and high-temperature storage performance of the battery can be further improved.

[0281] In some embodiments, M, X and Z each independently include one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, Mn and Al; and / or, the doping element in the doped carbon includes one or more elements selected from nitrogen, phosphorus, sulfur, boron and fluorine; and / or, M′ includes one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Co, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and may optionally include one or more elements selected from Mg, Al, Si, Zn, Zr and Sn; and / or, the polysiloxane is selected from one or more of a linear structure polysiloxane and a cyclic structure polysiloxane; and / or, the polysaccharide is selected from one or more of a plant polysaccharide and a marine polysaccharide.

[0282] By using the above-mentioned specific material as the coating layer, the dissolution of the Mn element can be further reduced, and the high-temperature cycle performance and high-temperature storage performance of the battery can be further improved.

[0283] In some embodiments, the second positive electrode active material includes a second core and a second shell covering the second core.

[0284] The second core includes Li m1 Mn1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 Includes one or more elements selected from B, S, Si and N.

[0285] The second shell includes a first coating layer coating the second inner core and a second coating layer coating the first coating layer, the first coating layer includes pyrophosphate MP2O7 and phosphate XPO4, M and X each independently include one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; the second coating layer contains carbon.

[0286] The second positive electrode active material may be a core-shell structure having two coating layers, and the element B doped at the transition metal position of the lithium-containing phosphate 2 It helps to reduce the lattice change rate of lithium-containing phosphates during lithium insertion and extraction, improve the structural stability of the second positive electrode active material, greatly reduce the dissolution of manganese and reduce the oxygen activity on the particle surface. 2 It helps to change the difficulty of the change of the Mn-O bond length, thereby reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the battery. The first coating layer of the second positive electrode active material includes pyrophosphate and phosphate. Since the migration barrier of transition metals in pyrophosphate is relatively high (>1eV), the dissolution of transition metals can be effectively reduced. Phosphates have excellent lithium ion conductivity and can reduce the surface impurity lithium content. In addition, since the second coating layer is a carbon-containing layer, it can effectively improve the conductivity and desolvation ability of lithium-containing phosphates. In addition, the "barrier" effect of the second coating layer can further reduce the migration of manganese ions into the electrolyte and reduce the corrosion of the electrolyte to the second active material. Therefore, by performing specific element doping and surface coating on lithium-containing phosphates, the dissolution of Mn elements in the lithium insertion process can be effectively reduced, while promoting the migration of lithium ions, thereby improving the rate performance of the battery and improving the cycle performance and high temperature performance of the battery.

[0287] In some embodiments, the second positive electrode active material includes a second core and a second shell covering the second core.

[0288] The second core includes Lim1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 Includes one or more elements selected from B, S, Si and N.

[0289] The second shell includes a first coating layer coating the second inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer.

[0290] The first coating layer includes pyrophosphate Li r QP2O7 and / or Q s (P2O7) t , 0≤r≤2, 1≤s≤4, 1≤t≤6, pyrophosphate Li r QP2O7 and / or Q s (P2O7) t The Qs in each independently include one or more elements selected from Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al.

[0291] The second coating layer includes crystalline phosphate XPO4, and X includes one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al.

[0292] The third coating layer includes carbon.

[0293] Therefore, the second positive electrode active material can improve the gram capacity and cycle performance of the battery.

[0294] The second positive electrode active material is a core-shell structure, wherein the transition metal site and P site of the second core are doped with element B 2 and element C 2, which can not only effectively reduce manganese dissolution, thereby reducing manganese ions migrating to the negative electrode, reducing the electrolyte consumed due to SEI film decomposition, and improving the battery's cycle performance, but also promote Mn-O bond adjustment, reduce lithium ion migration barriers, promote lithium ion migration, and improve the battery's rate performance; by coating the second core with a first coating layer including pyrophosphate, the migration resistance of manganese can be further increased, its dissolution can be reduced, and the surface impurity lithium content can be reduced, and the contact between the second core and the electrolyte can be reduced, thereby reducing interfacial side reactions, reducing gas production, and improving the battery's high-temperature storage performance and cycle performance; by further coating with a phosphate coating layer with excellent lithium ion conductivity, the interfacial side reactions on the surface of the second positive electrode active material can be effectively reduced, thereby improving the battery's high-temperature cycle and storage performance; by further coating with a carbon layer as the third coating layer, the battery's kinetic performance can be further improved. In addition, in the second core, the element B doped at the transition metal position 2 It also helps to reduce the lattice change rate of the lithium-containing phosphate in the process of lithium insertion and extraction, improve the structural stability of the second positive electrode active material, greatly reduce the dissolution of manganese and reduce the oxygen activity on the particle surface; the element C doped at the P position 2 It also helps to change the difficulty of the Mn-O bond length change, thereby improving electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the battery's rate performance.

[0295] In addition, the entire second core system maintains electrical neutrality, which can minimize defects and impurities in the second positive electrode active material. If there is an excess of transition metal (such as manganese) in the second positive electrode active material, since the material system itself has a relatively stable structure, the excess transition metal is likely to precipitate in the form of a single substance or form an impurity phase inside the lattice. Maintaining electrical neutrality can minimize such impurities. In addition, maintaining the electrical neutrality of the system can also generate lithium vacancies in the material in some cases, thereby making the kinetic performance of the second positive electrode active material more excellent.

[0296] In some embodiments, the one or more coating layers in the second shell that are farthest from the second core each independently include one or more selected from polysiloxane, polysaccharide, and polysaccharide derivatives.

[0297] As a result, the uniformity of the coating can be improved, and the interfacial side reactions caused by high voltage can be effectively blocked, thereby improving the high-temperature cycle performance and high-temperature storage performance of the second positive electrode active material; and the coating layer has good ionic conductivity, which helps to improve the gram capacity of the second positive electrode active material while reducing the heat generation of the battery.

[0298] In some embodiments, the polysiloxane comprises a structural unit represented by formula (i).

[0299]

[0300] R1 and R2 are independently selected from H, -COOH, -OH, -SH, -CN, -SCN, amino, phosphate, carboxylate, amide, aldehyde, sulfonyl, polyether segment, C1-C20 aliphatic, C1-C20 halogenated aliphatic, C1-C20 heteroaliphatic, C1-C20 halogenated heteroaliphatic, C6-C20 aromatic, C6-C20 halogenated aromatic, C2-C20 heteroaromatic and C2-C20 halogenated heteroaromatic.

[0301] Optionally, R1 and R2 are independently selected from H, amino, phosphate, polyether segment, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl and C2-C8 haloalkenyl.

[0302] In some embodiments, the polysiloxane further comprises an end-capping group, which includes one or more of the following functional groups: polyether, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl, C2-C8 haloalkenyl, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy, C2-C8 epoxy, hydroxyl, C1-C8 hydroxyalkyl, amino, C1-C8 aminoalkyl, carboxyl, C1-C8 carboxylalkyl.

[0303] In some embodiments, the polysiloxane includes polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl functionalized polysiloxane, epoxy-terminated polysiloxane, methoxy-terminated polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, polymethylchloropropylsiloxane, hydroxy-terminated polydimethylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, aminoethylaminopropyl polydimethylsiloxane, terminal polyether polydimethylsiloxane, side chain aminopropyl polysiloxane, One or more of aminopropyl-terminated polydimethylsiloxane, side chain phosphate grafted polydimethylsiloxane, side chain polyether grafted polydimethylsiloxane, 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, cyclic polymethylvinylsiloxane, hexadecylcyclooctasiloxane, tetradecamethylcycloheptasiloxane, and cyclic polydimethylsiloxane.

[0304] In some embodiments, the number average molecular weight of polysiloxane, polysaccharide and polysaccharide derivative is independently below 300,000, optionally 10,000 to 200,000, more optionally 20,000 to 120,000, further optionally 400 to 80,000.

[0305] The number average molecular weight of polysiloxane, polysaccharide and polysaccharide derivatives can be measured by methods known in the art, such as gel permeation chromatography (GPC). The testing instrument can be a PL-GPC 220 high temperature gel permeation chromatograph.

[0306] In some embodiments, the mass percentage of polar functional groups in the polysiloxane is α, 0≤α<50%, optionally, 5%≤α≤30%.

[0307] "The mass percentage of polar functional groups in polysiloxane" refers to the mass proportion of polar functional groups in R1, R2 and end groups in polysiloxane. Polar functional groups include -COOH, -OH, -SH, -CN, -SCN, amino groups (including -NH2, -NH-), phosphate groups, carboxylate groups (-COO-), amide groups (-CONH-), aldehyde groups (-CHO), sulfonyl groups (-S(=O)2-), polyether segments, halogens, alkoxy groups, and epoxy groups. One or more of the following. When the above polar functional groups are directly connected to silicon atoms, α means the mass fraction of these polar functional groups in polysiloxane; when the above polar functional groups are not directly connected to silicon atoms, α means the sum of the mass fractions of polar functional groups and divalent to tetravalent methyl groups (such as -CH2, -CH-, -C-, etc.) directly connected thereto in polysiloxane, where "divalent to tetravalent methyl groups" means carbon atoms directly connected to polar functional groups and located between polar functional groups and silicon atoms, as well as other non-polar functional groups connected to carbon atoms. Taking polymethyltrifluoropropylsiloxane as an example, α means the mass percentage of -CF3 therein, excluding ethylene therein; taking polymethylchloropropylsiloxane as an example, α means the mass percentage of -CH2Cl, excluding ethylene therein; taking hydroxypropyl-terminated polydimethylsiloxane as an example, α means the mass percentage of -CH2OH. The mass percentage of polar functional groups in the polysiloxane can be determined by methods known in the art, such as titration (eg, acid-base titration, redox titration, precipitation titration), infrared spectroscopy, and nuclear magnetic resonance spectroscopy.

[0308] In some embodiments, the substituents attached to the sugar units in the polysaccharides and polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH and its salts, -R-OH, -SO3H and its salts, -R-OH, -R-SO3H and its salts, sulfate, alkoxy, R represents an alkylene group, optionally representing a C1-C5 alkylene group.

[0309] Optionally, the substituents attached to the sugar units in the polysaccharides and polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH, -COOLi, -COONa, -COOK, -SO3H, -SO3Li, -SO3Na, -SO3K, -CH2-SO3H, -CH2-SO3Li, -CH2-SO3Na, -CH2-SO3K, methoxy, ethoxy.

[0310] The term "substituents attached to the sugar unit" includes all groups attached to the sugar unit backbone.

[0311] In some embodiments, the polysaccharide includes one or more selected from pectin, carboxymethyl starch, hydroxypropyl starch, dextrin, cellulose ether, carboxymethyl chitosan, hydroxyethyl cellulose, carboxymethyl cellulose, carboxypropyl methyl cellulose, guar gum, sesbania gum, gum arabic, lithium alginate, sodium alginate, potassium alginate, fucoidan, agar, carrageenan, carrageenan, xanthan gum and fenugreek gum.

[0312] In some embodiments, the mass percentage of the substituents attached to the sugar units in the polysaccharide and polysaccharide derivatives is independently 20% to 85%, and optionally 30% to 78%. The mass percentage of the substituents attached to the sugar units in the polysaccharide and polysaccharide derivatives can be determined by methods known in the art, such as titration (e.g., acid-base titration, redox titration, precipitation titration), infrared spectroscopy, and nuclear magnetic resonance spectroscopy.

[0313] In some embodiments, the lattice mismatch between the material of the second core and the material of the second shell is less than 10%, thereby enabling good contact between the second core and the second shell (or coating layer) to prevent the second shell (or coating layer) from falling off.

[0314] In some embodiments, based on the weight of the positive electrode active material, the manganese content is in the range of 10-35 wt %, optionally in the range of 13.3-33.2 wt %, more optionally in the range of 15-30 wt %, and further optionally in the range of 17-20 wt %.

[0315] In some embodiments, based on the weight of the positive electrode active material, the content of phosphorus is in the range of 12-25 wt %, optionally in the range of 15-20 wt %, and more optionally in the range of 16.8-19.5 wt %.

[0316] In some embodiments, based on the weight of the positive electrode active material, the weight ratio of manganese element to phosphorus element is in the range of 0.71-1.85, optionally 0.90-1.25, and more optionally 0.95-1.20.

[0317] In the case where manganese is contained only in the second core of the second positive electrode active material, the content of manganese may correspond to the content of the second core.

[0318] Limiting the content of manganese within the above range can further improve the stability and density of the second positive electrode active material, thereby improving the battery's cycling, storage and compaction properties; and can maintain a higher voltage platform, thereby improving the battery's energy density.

[0319] Limiting the content of phosphorus within the above range can effectively reduce the influence of small polaron conductivity on the conductivity of the second positive electrode active material, and can further improve the stability of the lattice structure, thereby improving the overall stability of the second positive electrode active material.

[0320] Limiting the weight ratio of manganese to phosphorus within the above range can further reduce manganese dissolution, improve the stability and gram capacity of the second positive electrode active material, and improve the cycle performance and storage performance of the battery; it can also reduce impurities, enable the second positive electrode active material to maintain a higher discharge voltage platform, and enable the battery to have a high energy density.

[0321] The measurement of manganese and phosphorus can be carried out by conventional technical means in the art. In particular, the following method is used to determine the content of manganese and phosphorus: the material is dissolved in dilute hydrochloric acid (concentration 10-30%), the content of each element of the solution is tested by ICP, and then the content of manganese is measured and converted to obtain its weight content.

[0322] In some embodiments, the surface of the second positive electrode active material is coated with one or more of carbon and doped carbon; alternatively, the surface of the second positive electrode active material is coated with carbon, thereby improving the conductivity of the second positive electrode active material.

[0323] In some embodiments, the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine, so as to facilitate the control of the performance of the doped carbon layer.

[0324] In some embodiments, the coating amount of the second shell (only one coating layer) is 0.1-6% by weight, based on the weight of the second core. The coating amount of the coating layer is preferably within the above range, which can fully coat the second core and further improve the kinetic performance of the battery without sacrificing the gram capacity of the second positive electrode active material.

[0325] In some embodiments, the coating amount of the first coating layer is greater than 0 and less than or equal to 7% by weight, can be selected as greater than 0 and less than or equal to 6% by weight, can be more selected as greater than 0 and less than or equal to 5.5% by weight or 4-5.6% by weight, can be further selected as greater than 0 and less than or equal to 2% by weight, based on the weight of the second kernel; and / or, the coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, can be selected as greater than 0 and less than or equal to 5.5% by weight, can be more selected as 2-4% by weight or 3-5% by weight, based on the weight of the second kernel; and / or, the coating amount of the third coating layer is greater than 0 and less than or equal to 6% by weight, can be selected as greater than 0 and less than or equal to 5.5% by weight, can be more selected as greater than 0 and less than or equal to 2% by weight, based on the weight of the second kernel.

[0326] In some embodiments, the second shell further includes a fourth coating layer coating the third coating layer and a fifth coating layer coating the fourth coating layer.

[0327] The coating amounts of the fourth coating layer and the fifth coating layer are independently 0.01-10 wt %, optionally 0.05-10 wt %, more optionally 0.1-5 wt %, further 0.1-2 wt %, based on the weight of the second core.

[0328] In the second positive electrode active material with a core-shell structure of the present application, the coating amount of each coating layer is preferably within the above range, thereby being able to fully coat the second inner core and further improve the battery's kinetic performance without sacrificing the gram capacity of the second positive electrode active material.

[0329] In some embodiments, the second shell is located on 40% to 90% of the surface of the second core, and optionally 60% to 80% of the surface, thereby fully covering the second core and improving the dynamic performance of the battery.

[0330] In some embodiments, the second shell (which is only one coating layer) has a thickness of 1-15 nm.

[0331] In some embodiments, the thickness of the first coating layer is 1-10nm, optionally 2-10nm; and / or the thickness of the second coating layer is 2-25nm, optionally 2-15nm, and more optionally 3-15nm; and / or the thickness of the third coating layer is 2-25nm, optionally 5-25nm.

[0332] In some embodiments, the thickness of the first coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, or any range thereof.

[0333] In some embodiments, the thickness of the second coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, or within any range of the above values.

[0334] In some embodiments, the thickness of the third coating layer may be about 2nm, about 3nm, about 4nm, about 5nm, about 6nm, about 7nm, about 8nm, about 9nm, about 10nm, about 11nm, about 12nm, about 13nm, about 14nm, about 15nm, about 16nm, about 17nm, about 18nm, about 19nm, about 20nm, about 21nm, about 22nm, about 23nm, about 24nm, about 25nm, or in any range of any of the above values.

[0335] The first coating layer has the above thickness range, which can further reduce the adverse effect on the kinetic properties of the second positive electrode active material.

[0336] The second coating layer has the above-mentioned thickness range, so that the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so the interface side reaction can be effectively reduced, thereby improving the high temperature performance of the battery.

[0337] The third coating layer has the above-mentioned thickness range, which can enhance the conductivity of the second positive electrode active material and improve the compaction density of the positive electrode sheet prepared using the second positive electrode active material.

[0338] The thickness test of the coating layer is mainly carried out by FIB. The specific method may include the following steps: randomly selecting a single particle from the second positive electrode active material powder to be tested, cutting a thin slice with a thickness of about 100nm from the middle position or near the middle position of the selected particle, and then performing TEM testing on the thin slice to measure the thickness of the coating layer, measuring 3-5 positions, and taking the average value.

[0339] In some embodiments, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, and oxide, and the one or more selected from pyrophosphate, phosphate, and oxide is crystalline.

[0340] Optionally, the crystallinity of the pyrophosphate, phosphate and oxide is each independently from 10% to 100%, more preferably from 50% to 100%.

[0341] Herein, crystalline means that the crystallinity is above 50%, i.e., 50%-100%. That is, when the crystalline pyrophosphate and crystalline phosphate of the present application appear, it means that the crystallinity is 50% to 100%.

[0342] Pyrophosphates and phosphates with a certain degree of crystallinity are not only conducive to fully utilizing the pyrophosphate coating to reduce manganese dissolution and the phosphate coating's excellent ability to conduct lithium ions and reduce interface side reactions, but also enable the pyrophosphate coating and the phosphate coating to better lattice match, thereby achieving a close bond between the coatings.

[0343] It should be noted that the crystallinity can be adjusted by adjusting the process conditions of the sintering process, such as the sintering temperature, the sintering time, etc. The crystallinity can be measured by methods known in the art, such as X-ray diffraction, density method, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance absorption method. The specific method of testing the crystallinity of the second positive electrode active material by X-ray diffraction method may include the following steps:

[0344] Take a certain amount of the second positive electrode active material powder and measure the total scattering intensity by X-ray. It is the sum of the scattering intensities of the entire space matter and is only related to the intensity of the primary rays, the chemical structure of the second positive electrode active material powder, and the total number of electrons participating in the diffraction, that is, the mass, but has nothing to do with the order state of the sample. Then separate the crystalline scattering and non-crystalline scattering from the diffraction pattern, and the degree of crystallinity is the ratio of the scattering of the crystalline part to the total scattering intensity.

[0345] In some embodiments, in the second shell, the weight ratio of pyrophosphate to phosphate and the weight ratio of pyrophosphate to oxide are independently 1:3 to 3:1, and can be 1:3 to 1:1. Thus, by having pyrophosphate and phosphate in a suitable weight ratio range or pyrophosphate and oxide in a suitable weight ratio range, manganese dissolution can be effectively reduced, surface impurity lithium content can be effectively reduced, and interface side reactions can be reduced, thereby improving the high temperature storage performance and high temperature cycle performance of the battery.

[0346] In some embodiments, one or more coating layers independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of SP2 carbon to SP3 carbon in the carbon is any value in the range of 0.07-13, and can be any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.

[0347] In some embodiments, the molar ratio of SP2 carbon to SP3 carbon may be about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, about 10, or any range of any of the above values.

[0348] In the present application, "about" a certain numerical value indicates a range, which means a range of ±10% of the numerical value.

[0349] By selecting the form of carbon in the carbon coating, the comprehensive electrical performance of the battery is improved. Specifically, by using a mixed form of SP2 carbon and SP3 carbon and limiting the ratio of SP2 carbon to SP3 carbon within a certain range, the following situations can be avoided: if the carbon in the coating is all amorphous SP3, the conductivity is poor; if it is all graphitized SP2, although the conductivity is good, there are few lithium ion pathways, which is not conducive to lithium deintercalation. In addition, limiting the molar ratio of SP2 carbon to SP3 carbon within the above range can not only achieve good conductivity, but also promote the transmission of lithium ions, which is beneficial to the realization of battery functions and its cycle performance.

[0350] The mixing ratio of the SP2 form and the SP3 form of carbon can be controlled by sintering conditions such as sintering temperature and sintering time. The molar ratio of SP2 form carbon to SP3 form carbon can be measured by Raman spectroscopy. The specific test method is as follows: by peak separation of the energy spectrum of the Raman test, Id / Ig (where Id is the peak intensity of the SP3 form carbon, and Ig is the peak intensity of the SP2 form carbon) is obtained to confirm the molar ratio of the two.

[0351] In some embodiments, one or more coating layers independently include doped carbon, and the mass content of the doped element in the doped carbon is less than 30%; optionally, the mass content of the doped element in the doped carbon is less than 20%. The doping element within the above content range can not only fully improve the conductivity of the pure carbon layer, but also effectively avoid excessive surface activity caused by excessive doping of the doping element, thereby effectively controlling the interface side reaction caused by excessive doping of the coating layer.

[0352] In some embodiments, one or more coating layers each independently include doped carbon, in which the doping elements are nitrogen and / or sulfur, and the mass content of the doping elements in the doped carbon is 1% to 15%; or, the doping elements are phosphorus, boron and / or fluorine, and the mass content of the doping elements in the doped carbon is 0.5% to 5%.

[0353] Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.

[0354] Since nitrogen atoms and sulfur atoms are closer to the atomic radius of carbon atoms and are not easy to destroy the carbon skeleton, when the doping amount of nitrogen atoms and sulfur atoms is within the above relatively wide range, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation ability can be promoted.

[0355] Since the atomic radius of phosphorus atoms, boron atoms and / or fluorine atoms is different from that of carbon atoms, excessive doping can easily destroy the carbon skeleton. Therefore, when the doping amount of phosphorus atoms, boron atoms and / or fluorine atoms is within the relatively small range mentioned above, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation capabilities can be promoted.

[0356] In some embodiments, one or more coating layers independently include pyrophosphate, the pyrophosphate has a lattice spacing range of 0.293-0.470 nm, optionally 0.297-0.462 nm or 0.293-0.326 nm, and more optionally 0.300-0.310 nm, and a crystal orientation (111) angle range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°.

[0357] In some embodiments, one or more coating layers independently include phosphate, the phosphate has a lattice spacing ranging from 0.244-0.425 nm, optionally 0.345-0.358 nm, and a crystal orientation (111) angle ranging from 20.00°-37.00°, optionally 24.25°-26.45°.

[0358] In some embodiments, the first coating layer or the second coating layer comprises a phosphate.

[0359] The first coating layer and the second coating layer in the second positive electrode active material are both made of crystalline materials, and their interplanar spacing and angle ranges are within the above ranges. Thus, the impurity phase in the coating layer can be effectively reduced, thereby improving the material's gram capacity, cycle performance, and rate performance.

[0360] In some embodiments, the lattice change rate of the second positive electrode active material before and after complete lithium deintercalation is less than 50%, optionally less than 9.8%, more optionally less than 8.1%, further optionally less than 7.5%, further optionally less than 6%, further optionally less than 4%, further optionally less than 3.8%, and further optionally between 2.0% and 3.8%.

[0361] By reducing the lattice change rate, Li ion transmission can be made easier, that is, the mobility of Li ions in the second positive electrode active material is stronger, which is beneficial to improve the rate performance of the battery. The lattice change rate can be measured by methods known in the art, such as X-ray diffraction (XRD).

[0362] In some embodiments, the Li / Mn antisite defect concentration of the second positive electrode active material is less than 5.3%, optionally less than 5.1%, more optionally less than 4%, further optionally less than 2.2%, further optionally less than 2%, further optionally less than 1.5%-2.2% or less than 0.5%.

[0363] The so-called Li / Mn antisite defect refers to the Li + With Mn 2+ The positions of Li / Mn are interchanged. The Li / Mn antisite defect concentration refers to the number of Li / Mn antisite defects in the second positive electrode active material. 2+ The exchanged Li + Occupy + The percentage of total antisite defect Mn 2+ Will hinder Li + The transport of Li / Mn antisite defects can improve the gram capacity and rate performance of the second positive electrode active material by reducing the concentration of Li / Mn antisite defects. The concentration of Li / Mn antisite defects can be measured by methods known in the art, such as XRD.

[0364] In some embodiments, the surface oxygen valence state of the second positive electrode active material is below -1.55, optionally below -1.82, more optionally below -1.88, further optionally below -1.90 or -1.98 to -1.88, further optionally -1.98 to -1.89, further optionally -1.98 to -1.90.

[0365] By reducing the surface oxygen valence state, the interfacial side reaction between the second positive electrode active material and the electrolyte can be reduced, thereby improving the cycle performance and high temperature stability of the battery. The surface oxygen valence state can be measured by methods known in the art, such as by electron energy loss spectroscopy (EELS).

[0366] The first positive electrode active material and the second positive electrode active material may be tested for element content using inductively coupled plasma emission spectroscopy (ICP).

[0367] The first positive electrode active material and the second positive electrode active material may be prepared by a sintering method. When the first positive electrode active material and the second positive electrode active material have a shell, the shells of the first positive electrode active material and the second positive electrode active material may be prepared by a liquid phase coating method.

[0368] The positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.

[0369] In some embodiments, the total content of the positive electrode active material in the positive electrode film layer is 50-99.5% by weight, optionally 90-99.5% by weight, or 95-99.5% by weight, based on the total weight of the positive electrode film layer.

[0370] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0371] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0372] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0373] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the first positive electrode active material, the second positive electrode active material, the positive electrode conductor, the positive electrode binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0374] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0375] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0376] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0377] In some embodiments, the negative electrode active material may adopt materials known in the art. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0378] In some embodiments, the negative electrode film layer may further include a negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0379] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0380] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC)).

[0381] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0382] In some embodiments, the negative electrode plate may not include a negative electrode active material capable of deintercalating and extracting lithium ions. For example, the negative electrode plate may include a lithium plate or a lithium alloy plate; or, the negative electrode plate may include a mesh or foam three-dimensional skeleton layer; or, the negative electrode plate may include a negative electrode current collector and a lithium-containing layer disposed on at least one surface of the negative electrode current collector.

[0383] The present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments, the isolation membrane includes a porous substrate. The material of the porous substrate may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene, polyester, and polyimide. The porous substrate can be a single-layer film or a multi-layer composite film, without particular restrictions. When the porous substrate is a multi-layer composite film, the materials of each layer can be the same or different, without particular restrictions.

[0384] In some embodiments, the isolation membrane may further include a coating layer located on at least one surface of the porous substrate. Optionally, the coating layer includes one or more of inorganic heat-resistant particles and organic heat-resistant particles.

[0385] Preparation method

[0386] The embodiment of the present application also provides a method for preparing the above-mentioned battery cell.

[0387] The method comprises the following steps: providing a battery container containing a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises a first positive electrode active material and a second positive electrode active material, the first positive electrode active material and the second positive electrode active material can extract and embed lithium ions, the first positive electrode active material comprises a Ni element, the second positive electrode active material comprises a Fe element, the first positive electrode active material and the second positive electrode active material have different crystal forms, and the specific surface area of ​​the first positive electrode active material is smaller than the specific surface area of ​​the second positive electrode active material, based on the total weight of the positive electrode active material, the weight content of the first positive electrode active material is recorded as w1, and the weight content of the second positive electrode active material is recorded as w2; uniformly mixing a non-aqueous solvent, an electrolyte salt and a first additive to obtain an electrolyte, the electrolyte salt comprises a first cation and a first anion, the first additive comprises a second cation and a second anion, and the second anion comprises HPO4 2- 、H2PO4 - The weight content of the first anion in the electrolyte is recorded as w a The weight content of the second anion in the electrolyte is recorded as w b, all based on the total weight of the electrolyte; injecting the obtained electrolyte into a battery container to obtain a battery cell, and the battery cell satisfies 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0.

[0388] The method provided in the embodiment of the present application can prepare the above-mentioned battery cell. Other parameters of the battery cell can refer to the battery cell mentioned above in the present application and will not be described in detail here.

[0389] In some embodiments, the battery container further includes a separator.

[0390] In some embodiments, the method may further include the following steps: forming an electrode assembly by winding the positive electrode sheet, the separator and the negative electrode sheet through a winding process and / or a lamination process, and placing the electrode assembly in a battery container.

[0391] The battery container may be an outer package. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0392] In some embodiments, after the obtained electrolyte is injected into the battery container, it can also go through processes such as standing, formation, aging, and capacity testing to obtain a battery cell.

[0393] Multiple battery cells may be further connected in series, in parallel, or in a hybrid connection to form a battery module. Multiple battery modules may be connected in series, in parallel, or in a hybrid connection to form a battery pack. In some embodiments, multiple battery cells may also be directly connected to form a battery pack.

[0394] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0395] The electric device can select the type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.

[0396] Figure 6Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0397] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0398] Example

[0399] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0400] Examples 1 to 16 and Comparative Examples 1 to 6 were prepared according to the following method.

[0401] Preparation of positive electrode

[0402] The positive electrode active material, positive electrode conductive agent carbon black, and positive electrode binder polyvinylidene fluoride (PVDF) shown in Table 1 were fully stirred and mixed in an appropriate amount of solvent NMP at a weight ratio of 90:5:5 to form a uniform positive electrode slurry; the positive electrode slurry was evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0403] The positive electrode active material includes a first positive electrode active material and a second positive electrode active material, and the first positive electrode active material and the second positive electrode active material can be prepared by a sintering method. In Table 1, the weight content w1 of the first positive electrode active material and the weight content w2 of the second positive electrode active material are both based on the total weight of the positive electrode active material. The first positive electrode active material and the second positive electrode active material can be commercially available or prepared according to methods known in the art.

[0404] The weight content of Ni in the positive electrode film is recorded as w Ni The weight content of Fe in the positive electrode film is recorded as w Fe , are based on the total weight of the positive electrode film layer.

[0405] w Ni and w FeThe test can be carried out as follows: take about 0.4g (accurate to 0.0001g) of the positive electrode film material into a 25ml beaker, add 2-5ml nitric acid and leave it overnight, then place the beaker on an electric hot plate, heat at about 100°C (the input voltage can be adjusted by a voltage-regulating transformer to control the temperature) until the positive electrode active material is digested, then add 0.5ml perchloric acid, heat and digest at about 140°C until the white smoke is gone, the residue should be white, otherwise nitric acid and perchloric acid should be added again to repeat the digestion, finally use 7% (volume % of acid) hydrochloric acid to dissolve the extraction solution, then dilute the obtained solution to an appropriate volume and use an inductively coupled plasma emission spectrometer ICP-OES to test the content of Ni and Fe elements in the positive electrode film.

[0406] Preparation of negative electrode

[0407] The negative electrode active material graphite, the negative electrode binder styrene-butadiene rubber (SBR), the negative electrode thickener sodium carboxymethyl cellulose (CMC), and the negative electrode conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 90:3:2:5 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0408] Isolation film

[0409] A porous polyethylene (PE) film is used as the isolation membrane.

[0410] Preparation of electrolyte

[0411] Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 to obtain a non-aqueous solvent, and then the electrolyte salt and the first additive shown in Table 1 were dissolved in the non-aqueous solvent, and then FEC was added to prepare an electrolyte. The concentration of the electrolyte salt was 1 mol / L, and the content of FEC was 5%, based on the total weight of the electrolyte. / indicates that the corresponding component was not added.

[0412] The electrolyte salt includes a first cation and a first anion, the first additive includes a second cation and a second anion, and the weight content of the first anion in the electrolyte is recorded as w a The weight content of the second anion in the electrolyte is recorded as w b , are based on the total weight of the electrolyte.

[0413] w b / (w a +w b ) can be tested by ion chromatography. The test standard can refer to GB / T36240-2018.

[0414] Preparation of batteries

[0415] The positive electrode sheet, the isolation film, and the negative electrode sheet are made into an electrode assembly according to a Z-shaped stacking structure, and then vacuum dried at 90°C for 12 hours, and then the tabs are welded (the positive electrode uses an aluminum tab, the negative electrode uses a nickel tab, and the positive and negative tabs are located at the same end of the electrode assembly). The electrode assembly after welding the tabs is placed in an aluminum-plastic film of a suitable size for top and side sealing, and then the battery is obtained after the processes of liquid injection, standing, formation, aging, exhaust, secondary sealing, and capacity testing.

[0416] Test Section

[0417] (1) 25℃ Cyclic Performance Test

[0418] Under a constant temperature environment of 25°C, the prepared battery is charged to 4.4V at a constant current of 0.5C, then charged to a current of ≤0.05C at a constant voltage of 4.4V, left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C. This is a cycle charge and discharge process, and the discharge capacity at this time is recorded as the discharge capacity of the first cycle. The battery is subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle is recorded until the discharge capacity of the battery decays to 80% of the discharge capacity of the first cycle. The cycle number at this time is used to characterize the cycle performance of the battery. The higher the number of cycles of the battery, the better the cycle performance.

[0419] (2) Battery internal resistance growth rate test after 500 cycles

[0420] Under a constant temperature environment of 25°C, the prepared battery was charged at a constant current of 0.5C to 4.4V, and then charged at a constant voltage of 4.4V to a current ≤0.05C, and allowed to stand for 30 minutes. At this time, the voltage of the battery was recorded as V1; the battery was discharged at a constant current of 1C for 30 seconds, and the voltage at the end of the discharge was recorded as V2. The internal resistance DCR of the battery before the cycle was recorded, DCR = (V1-V2) / 1C.

[0421] The battery was cycled 500 times according to the above cycle performance test method, and the internal resistance DCR of the battery after 500 cycles was tested according to the above method.

[0422] The internal resistance growth rate of the battery after 500 cycles = (internal resistance after 500 cycles / internal resistance before the cycle)-1.

[0423] (3) HF content test in electrolyte

[0424] Disassemble the battery after 500 cycles to obtain the residual electrolyte. Turn on the power of the fume hood, and turn on the lighting and exhaust functions at the same time; rinse the burette with triethylamine standard solution 3 times, weigh 10-15g of electrolyte sample and add it to a 100ml beaker, add color indicator (neutral red indicator and methylene blue dye mixture), and the solution is purple at this time; titrate the sample to be tested with triethylamine standard solution until the solution turns green, and stop titrating. HF content in electrolyte = (V1-V2) × C / m, V2 is the volume of the burette at the end of titration; V1 is the volume of the burette before titration; C is the concentration of the triethylamine solution, in mol / L; m is the mass of the weighed electrolyte sample, in g.

[0425]

[0426]

[0427] From the test results in Table 1 and Table 2, it can be seen that by adjusting the weight content of the first anion in the electrolyte w a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, the amount of the second anion can be better matched with the amount of the first positive electrode active material and the second positive electrode active material, thereby reducing the internal resistance growth rate during the battery cycle, reducing the acidity of the electrolyte, and making the battery have good cycle performance.

[0428] When 100×(w1 / w2)×[w b / (w a +w b )] is less than 0.99, the content of the second anion is small and the water content in the electrolyte is high, so the second anion has a poor neutralization effect on the hydrofluoric acid in the electrolyte. A large amount of hydrofluoric acid in the electrolyte will destroy the structure of the positive electrode active material, especially the surface structure of the first positive electrode active material, which leads to a high internal resistance growth rate and poor cycle performance during the battery cycle.

[0429] When 100×(w1 / w2)×[w b / (w a +w b)] is greater than 19.0, the content of the second anion is large and the water content in the electrolyte is small. At this time, more second anions participate in the formation of the SEI film, which will cause the stability of the SEI film to deteriorate, thereby increasing the irreversible capacity of the battery on the one hand, and increasing the internal resistance growth rate during the battery cycle on the other hand; at the same time, after the battery is charged and discharged for multiple cycles, the stability of the SEI film deteriorates and the side reactions of the battery increase, which will also increase the HF content in the electrolyte after the cycle and the acidity of the electrolyte, thereby further increasing the internal resistance growth rate during the battery cycle.

[0430] Examples 17 to 21

[0431] The preparation method of the battery is similar to that of Example 5, except that the specific surface area of ​​the second positive electrode active material is different. The specific parameters and test results are detailed in Table 3.

[0432] Table 3

[0433]

[0434] From the test results in Table 3, it can be seen that when other conditions are the same, the performance of the prepared batteries varies depending on the specific surface area of ​​the second positive electrode active material. a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, which can reduce the HF content of the electrolyte after cycling and make the battery have a low internal resistance growth rate and a long cycle life.

[0435] It can also be seen from the test results in Table 3 that the specific surface area of ​​the second positive electrode active material is 11-18.4 m 2 / g, optional 11.9-15.0m 2 / g, it is beneficial for the battery to have a lower internal resistance growth rate and a longer cycle life.

[0436] Examples 22 to 25

[0437] The preparation method of the battery is similar to that of Example 3, except that the types of the electrolyte salt and the first additive in the electrolyte are different. The specific parameters and test results are detailed in Table 4.

[0438] Table 2

[0439]

[0440] From the test results in Table 4, it can be seen that when other conditions are the same, the performance of the prepared batteries varies with the type of electrolyte salt and / or the first additive. a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, which can reduce the HF content of the electrolyte after cycling and make the battery have a low internal resistance growth rate and a long cycle life.

[0441] Examples 26 to 30

[0442] The preparation method of the battery is similar to that of Example 5, except that the type of the second positive electrode active material is different. The specific parameters and test results are detailed in Table 5. The second positive electrode active material can be prepared by a method known in the art, such as a sintering method.

[0443] Table 5

[0444]

[0445] From the test results in Table 5, it can be seen that the performance of the prepared batteries varies with the type of the second positive electrode active material. a , the weight content of the second anion in the electrolyte w b , the weight content w1 of the first positive electrode active material in the positive electrode active material, and the weight content w2 of the second positive electrode active material in the positive electrode active material, and satisfy 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.0, which can reduce the HF content of the electrolyte after cycling and make the battery have a low internal resistance growth rate and a long cycle life.

[0446] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A battery cell, comprising a positive electrode plate and an electrolyte, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material and the second positive electrode active material are capable of extracting and inserting lithium ions, the first positive electrode active material includes a Ni element, the second positive electrode active material includes a Fe element, the first positive electrode active material and the second positive electrode active material have different crystal forms, and the specific surface area of ​​the first positive electrode active material is smaller than the specific surface area of ​​the second positive electrode active material; The electrolyte includes a non-aqueous solvent, an electrolyte salt, and a first additive, wherein the electrolyte salt includes a first cation and a first anion, the first additive includes a second cation and a second anion, and the second anion includes HPO4 2- 、H2PO4 - One or both of the following: The weight content of the first anion in the electrolyte is recorded as w a The weight content of the second anion in the electrolyte is recorded as w b , are based on the total weight of the electrolyte; Based on the total weight of the positive electrode active material, the weight content of the first positive electrode active material is recorded as w1, and the weight content of the second positive electrode active material is recorded as w2; and the battery cell satisfies 0.99≤100×(w1 / w2)×[w b / (w a +w b )]≤19.

0.

2. The battery cell according to claim 1, characterized in that: 1.17≤100×(w1 / w2)×[w b / (w a +w b )]≤16.33, optionally, 2.00≤100×(w1 / w2)×[w b / (w a +w b )]≤11.

67.

3. The battery cell according to any one of claims 1 to 2, characterized in that: w1 is 33.5%-95%, optionally, w1 is 50%-70%; and / or, w2 is 5%-66.5%, optionally, w2 is 30%-50%; and / or, 0.5%≤w b / (w a +w b )≤5.5%, optionally, 1.5%≤w b / (w a +w b )≤4.5%.

4. The battery cell according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the first positive electrode active material is 0.5-1 m 2 / g, optional 0.6-0.9m 2 / g; and / or, The specific surface area of ​​the second positive electrode active material is 11-18.4 m 2 / g, optional 11.9-15.0m 2 / g.

5. The battery cell according to any one of claims 1 to 4, characterized in that: The first cation comprises a lithium ion; and / or, The first anion includes PF6 - 、ClO4 - 、AsF6 - 、BF4 - 、N(CF3SO2)2 - CF3SO3 - 、N(FSO2)2 - 、C(SO2CF3)3 - PO2F2 - , one or more of difluorooxalatoborate ion, dioxalatoborate ion, difluorooxalatophosphate ion, and tetrafluorooxalatophosphate ion.

6. The battery cell according to any one of claims 1 to 5, characterized in that: The second cation includes one or more of lithium ions and Me ions, and the Me ions include one or more of sodium ions, potassium ions, calcium ions, and magnesium ions.

7. The battery cell according to any one of claims 1 to 6, characterized in that: The weight content of Ni in the positive electrode film is recorded as w Ni , based on the total weight of the positive electrode film layer, 10.2%≤w Ni ≤28.8%, optionally, 15.1%≤w Ni ≤ 21.2%; and / or, The weight content of Fe element in the positive electrode film is recorded as w Fe , based on the total weight of the positive electrode film layer, 1.2% ≤ w Fe ≤11.1%, optionally, 3.9%≤w Fe ≤8.7%.

8. The battery cell according to any one of claims 1 to 7, characterized in that: The first positive electrode active material includes a layered oxide containing lithium; Optionally, the first positive electrode active material comprises a compound represented by formula (I), Li a A 1 b Ni c Co d B 1 e C 1 f O g D 1 h (I), A 1 It includes one or more elements selected from Group IA, Group IIA, Group VIII, Group VIB, and Group IIB, and may optionally include one or more elements selected from Na, K, Mg, Rb, Zn, and Zr; B 1 including Mn and / or Al; C 1 The invention comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB and Group VIII, and may be selected from Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Cu, Ba, Mo, V, Ce, Nb, Sb, Ta, Ge, Nb, Sc, Ba, B, S and Y, and may be selected from Mg, Ti, W, Zr, Cr, Zn, Cu, V, Nb, Sr, Sb and Y. 1 The invention comprises one or more elements selected from Group VIA and Group VIIA, and may be selected from one or more elements selected from N, S, F, Cl and Br, and may be selected from S and / or F; a is selected from the range of 0.75 to 1.2, and may be selected from the range of 0.9 to 1.1; b is selected from the range of 0 to 0.2, and may be selected from the range of 0 to 0.1; c is selected from the range of 0.500 to 0.990, and may be selected from the range of 0.500 to 0.600; d is selected from the range of 0 to 0.490, and may be selected from the range of 0 to 0.100; e is selected from the range of 0.001 to 0.490, and may be selected from the range of 0.300 to 0.450; f is selected from the range of 0 to 0.1, and may be selected from the range of 0.001 to 0.05; g is selected from the range of 1.0 to 2.0, and may be selected from the range of 1.9 to 2.0; h is selected from the range of 0 to 1.0, and may be selected from the range of 0.01 to 0.1; Optionally, c+d+e+f=1; and / or, Optionally, g+h=2.

9. The battery cell according to claim 8, characterized in that: The first positive electrode active material includes a first core and a first shell covering the first core. The first core comprises a compound represented by formula (I); The first shell comprises one or more coating layers, each coating layer having ionic conductivity and / or electronic conductivity; Optionally, the one or more coating layers each independently include one or more selected from phosphate, pyrophosphate, carbon, doped carbon, oxide, and fast ion conductor, and more optionally include one or more selected from phosphate, pyrophosphate, and oxide.

10. The battery cell according to claim 9, characterized in that: The coating amount of the first shell is 0.005-1% by weight, and optionally 0.01-0.5% by weight, based on the weight of the first core; and / or, The thickness of the first shell is 2-200 nm, and can be optionally 5-50 nm.

11. The battery cell according to any one of claims 1 to 10, characterized in that: The second positive electrode active material includes a lithium-containing phosphate, Optionally, the second positive electrode active material comprises a compound represented by formula (II), Li m1 A 2 x1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O 4-n1 D 2 n1 (II), A 2 It includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB and Group VIB, and may be selected from one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and may be selected from one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; B 2 The invention comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB and Group VIII, and may be selected from one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge; C 2 It includes one or more elements selected from Group IIIA, Group IVA, Group VA and Group VIA, and may optionally include one or more elements selected from Group B, S, Si and N; D 2 The invention comprises one or more elements selected from Group VIA and Group VIIA, and may be selected from one or more elements selected from S, F, Cl and Br; m1 is selected from the range of 0.85 to 1.15, may be selected from the range of 0.9 to 1.1, and may be selected from the range of 0.97 to 1.01; x1 is selected from the range of 0 to 0.1, may be selected from the range of 0.001 to 0.1, and may be selected from the range of 0.001 to 0.005; y1 is selected from the range of 0 to 0.5, may be selected from the range of 0.001 to 0.5, and may be selected from the range of 0.005 to 0.2 range; y2 is selected from the range of 0.1 to 1, and can be selected from the range of 0.2 to 0.9, and can be selected from the range of 0.3 to 0.7; 1-y1-y2 is selected from the range of 0 to 0.9, and can be selected from the range of 0.05 to 0.75, and can be selected from the range of 0.22 to 0.68; z1 is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1, and can be selected from the range of 0.001 to 0.005; n1 is selected from the range of 0 to 0.5, and can be selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.

005.

12. The battery cell according to claim 11, characterized in that: A 2 comprising any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally comprising any one element selected from Mg and Nb; and / or, B 2 comprising one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally comprising at least two elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, and more optionally comprising at least two elements selected from Ti, V, Co and Mg, and further optionally comprising at least two elements selected from Ti, V, Co and Mg, and further optionally comprising more than one element selected from Ti, V, Co and Mg; and / or, C 2 comprising any one element selected from B, S, Si and N, optionally S; and / or, D 2 The element comprises any one element selected from S, F, Cl and Br, and F is optional.

13. The battery cell according to any one of claims 11 to 12, characterized in that: y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75 , x1 is selected from the range of 0.001 to 0.1, z1 is selected from the range of 0.001 to 0.5, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is 0, and n1 is selected from the range of 0.001 to 0.1; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9 , 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is 0, z1 is selected from the range of 0.001 to 0.5, and n1 is 0; or, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, x1 is selected from the range of 0.001 to 0.1, z1 is selected from the range of 0.001 to 0.5, and n1 is selected from the range of 0.001 to 0.

1.

14. The battery cell according to any one of claims 11 to 12, characterized in that: z1:n1 is selected from the range of 0.002 to 500, can be selected from the range of 0.2 to 100, and can be further selected from the range of 0.2 to 50.

15. The battery cell according to any one of claims 11 to 14, characterized in that: A 2 comprising one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; B 2 Includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge; C 2 including one or more elements selected from B, S, Si and N; D 2 It includes one or more elements selected from S, F, Cl and Br; m1 is selected from the range of 0.9 to 1.1, x1 is selected from the range of 0.001 to 0.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is selected from the range of 0.001 to 0.

1.

16. The battery cell according to any one of claims 11 to 14, characterized in that: B 2 It includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Co, Ga, Sn, Sb, Nb and Ge, and may optionally include one or more elements selected from Zn, Ti, V, Co and Mg; C 2 It includes one or more elements selected from B, Si, N and S; m1 is selected from the range of 0.9 to 1.1, x1 is 0, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, and n1 is 0.

17. The battery cell according to any one of claims 11 to 15, characterized in that: a1:x1 is in the range of 1 to 1200, and can be optionally in the range of 9 to 1100, and can be further optionally in the range of 190-998.

18. The battery cell according to any one of claims 11 to 17, characterized in that: z1: (1-z1) is 1:9 to 1:999, and can be optionally 1:499 to 1:

249.

19. The battery cell according to any one of claims 11 to 18, characterized in that: The second positive electrode active material includes a second core and a second shell covering the second core, The second core comprises the compound represented by formula (II); The second shell comprises one or more coating layers; each coating layer has ionic conductivity and / or electronic conductivity; Optionally, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

20. The battery cell according to claim 19, characterized in that: The second shell comprises a coating layer; optionally, the coating layer comprises one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.

21. The battery cell according to claim 19, characterized in that: The second shell includes a first coating layer covering the second core and a second coating layer covering the first coating layer; Optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer; More optionally, the first coating layer includes one or more selected from pyrophosphate, phosphate, oxide and boride, and the second coating layer includes one or more selected from carbon and doped carbon.

22. The battery cell according to claim 19, characterized in that: The second shell includes a first coating layer covering the second core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; Optionally, the first coating layer, the second coating layer and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer; More optionally, the first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphates, oxides and borides, and the third coating layer includes one or more selected from carbon and doped carbon.

23. The battery cell according to any one of claims 19 to 22, characterized in that: The pyrophosphate is M i (P2O7) j and / or, The phosphate is X p (PO4) q and / or, The doping element in the doped carbon includes one or more elements selected from Group IIIA, Group VA, Group VIA and Group VIIA; and / or, The oxide is M' k O l and / or, The boride is Z v B w and / or, The polymer includes one or more selected from polysaccharides and their derivatives, and polysiloxanes; M, X and Z each independently include one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; i is selected from the range of 1 to 4; j is selected from the range of 1 to 6; p is selected from the range of 1 to 2; q is selected from the range of 1 to 4; M′ comprises one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb; k is greater than 0 and less than or equal to 2; l is greater than 0 and less than or equal to 5; v is selected from the range of 1 to 7; w is selected from the range of 1 to 2.

24. The battery cell according to claim 23, characterized in that: M, X and Z each independently include one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, Mn and Al; and / or, The doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; and / or, M′ comprises one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Co, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and may optionally comprise one or more elements selected from Mg, Al, Si, Zn, Zr and Sn; and / or The polysiloxane is selected from one or more of linear polysiloxane and cyclic polysiloxane; and / or, The polysaccharide is selected from one or more of plant polysaccharides and marine polysaccharides.

25. The battery cell according to claim 19, characterized in that: The second positive electrode active material includes a second core and a second shell covering the second core, The second core includes Li m1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 including one or more elements selected from B, S, Si and N; The second shell includes a first coating layer coating the second inner core and a second coating layer coating the first coating layer, the first coating layer includes pyrophosphate MP2O7 and phosphate XPO4, M and X each independently include one or more elements selected from Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; the second coating layer contains carbon.

26. The battery cell according to claim 19, characterized in that: The second positive electrode active material includes a second core and a second shell covering the second core, The second core includes Li m1 Mn 1-y1-y2 Fe y2 B 2 y1 P 1-z1 C 2 z1 O4, m1 is selected from the range of 0.9 to 1.1, y1 is selected from the range of 0.001 to 0.5, y2 is selected from the range of 0.2 to 0.9, 1-y1-y2 is selected from the range of 0.05 to 0.75, z1 is selected from the range of 0.001 to 0.1, B 2 It includes one or more elements selected from Ti, V, Zr, Mg, Co, Ga, Sn, Sb, Nb and Ge, C 2 including one or more elements selected from B, S, Si and N; The second shell includes a first coating layer covering the second core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer. The first coating layer includes pyrophosphate Li r QP2O7 and / or Q s (P2O7) t , 0≤r≤2, 1≤s≤4, 1≤t≤6, the pyrophosphate Li r QP2O7 and / or Q s (P2O7) t wherein Q each independently comprises one or more elements selected from Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; The second coating layer comprises crystalline phosphate XPO4, wherein X comprises one or more elements selected from the group consisting of Li, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; The third coating layer includes carbon.

27. The battery cell according to any one of claims 19 to 26, characterized in that: The one or more coating layers in the second shell that are farthest from the second core each independently include one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.

28. The battery cell according to any one of claims 23 to 27, characterized in that: The polysiloxane comprises a structural unit represented by formula (i), R1 and R2 are independently selected from H, -COOH, -OH, -SH, -CN, -SCN, amino, phosphate, carboxylate, amide, aldehyde, sulfonyl, polyether segment, C1-C20 aliphatic, C1-C20 halogenated aliphatic, C1-C20 heteroaliphatic, C1-C20 halogenated heteroaliphatic, C6-C20 aromatic, C6-C20 halogenated aromatic, C2-C20 heteroaromatic and C2-C20 halogenated heteroaromatic; Optionally, R1 and R2 are independently selected from H, amino, phosphate, polyether segment, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl and C2-C8 haloalkenyl.

29. The battery cell according to any one of claims 23 to 28, characterized in that: The polysiloxane further comprises an end-capping group, which comprises one or more of the following functional groups: polyether, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl, C2-C8 haloalkenyl, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy, C2-C8 epoxy, hydroxyl, C1-C8 hydroxyalkyl, amino, C1-C8 aminoalkyl, carboxyl, C1-C8 carboxylalkyl.

30. The battery cell according to any one of claims 23 to 29, characterized in that: The polysiloxane comprises polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl functionalized polysiloxane, epoxy-terminated polysiloxane, methoxy-terminated polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, polymethylchloropropylsiloxane, hydroxy-terminated polydimethylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, aminoethylaminopropyl polydimethylsiloxane, terminal polyether polydimethylsiloxane, side-chain aminopropyl polysiloxane, aminopropyl One or more of end-capped polydimethylsiloxane, side chain phosphate grafted polydimethylsiloxane, side chain polyether grafted polydimethylsiloxane, 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, cyclic polymethylvinylsiloxane, hexadecylcyclooctasiloxane, tetradecamethylcycloheptasiloxane, and cyclic polydimethylsiloxane.

31. The battery cell according to any one of claims 23 to 30, characterized in that: The number average molecular weight of the polysiloxane, the polysaccharide and the polysaccharide derivative is independently below 300,000, and may be 10,000 to 200,000, more preferably 20,000 to 120,000, and further preferably 400 to 80,000.

32. The battery cell according to any one of claims 23 to 31, characterized in that: The mass percentage of the polar functional groups in the polysiloxane is α, 0≤α<50%, optionally, 5%≤α≤30%.

33. The battery cell according to any one of claims 23 to 32, characterized in that: The substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH and salts thereof, -R-OH, -SO3H and salts thereof, -R-OH, -R-SO3H and salts thereof, sulfate, alkoxy, R represents an alkylene group, optionally representing a C1-C5 alkylene group; Optionally, the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives each independently include one or more of the group consisting of the following functional groups: -OH, -COOH, -COOLi, -COONa, -COOK, -SO3H, -SO3Li, -SO3Na, -SO3K, -CH2-SO3H, -CH2-SO3Li, -CH2-SO3Na, -CH2-SO3K, methoxy, ethoxy.

34. The battery cell according to any one of claims 23 to 33, characterized in that: The polysaccharide includes one or more selected from pectin, carboxymethyl starch, hydroxypropyl starch, dextrin, cellulose ether, carboxymethyl chitosan, hydroxyethyl cellulose, carboxymethyl cellulose, carboxypropyl methyl cellulose, guar gum, sesbania gum, gum arabic, lithium alginate, sodium alginate, potassium alginate, fucoidan, agar, carrageenan, carrageenan, xanthan gum and fenugreek gum.

35. The battery cell according to any one of claims 23 to 34, characterized in that: The mass percentage of the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives is independently 20% to 85%, and optionally 30% to 78%.

36. The battery cell according to any one of claims 19 to 35, characterized in that: The lattice mismatch between the material of the second core and the material of the second shell is less than 10%.

37. The battery cell according to any one of claims 11 to 36, characterized in that: Based on the total weight of the second positive electrode active material, The manganese content is in the range of 10-35 wt %, optionally in the range of 13.3-33.2 wt %, more optionally in the range of 15-30 wt %, further optionally in the range of 17-20 wt %; and / or, The phosphorus content is in the range of 12-25 wt %, optionally in the range of 15-20 wt %, and more preferably in the range of 16.8-19.5 wt %; and / or, The weight ratio of manganese element to phosphorus element ranges from 0.71 to 1.85, and can be selected from 0.90 to 1.25, and more preferably from 0.95 to 1.

20.

38. The battery cell according to any one of claims 1 to 18, characterized in that: The surface of the second positive electrode active material is coated with one or more of carbon and doped carbon; optionally, the surface of the second positive electrode active material is coated with carbon.

39. The battery cell according to claim 38, characterized in that The doping elements in the doped carbon include one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine.

40. The battery cell according to any one of claims 19-20, 23-24, 27-39, characterized in that: The coating amount of the second shell is 0.1-6 wt % based on the weight of the second core.

41. The battery cell according to any one of claims 19, 21-37, characterized in that: The coating amount of the first coating layer is greater than 0 and less than or equal to 7% by weight, and can be greater than 0 and less than or equal to 6% by weight, and can be greater than 0 and less than or equal to 5.5% by weight or 4-5.6% by weight, and can be further greater than 0 and less than or equal to 2% by weight, based on the weight of the second core; and / or, The coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally 2-4% by weight or 3-5% by weight, based on the weight of the second core; and / or, The coating amount of the third coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the second core.

42. The battery cell according to any one of claims 19, 22-24, 26-37, and 41, characterized in that: The second shell further includes a fourth coating layer covering the third coating layer and a fifth coating layer covering the fourth coating layer; The coating amounts of the fourth coating layer and the fifth coating layer are independently 0.01-10 wt %, optionally 0.05-10 wt %, more optionally 0.1-5 wt %, further 0.1-2 wt %, based on the weight of the second core.

43. The battery cell according to any one of claims 19 to 42, characterized in that: The second shell is located on 40% to 90% of the surface of the second core, optionally 60% to 80% of the surface.

44. The battery cell according to any one of claims 19-20, 23-24, 27-40, 43, characterized in that: The thickness of the second shell is 1-15 nm.

45. The battery cell according to any one of claims 19, 21-37, 41-43, characterized in that: The thickness of the first coating layer is 1-10 nm, and can be 2-10 nm; and / or, The thickness of the second coating layer is 2-25 nm, optionally 2-15 nm, more optionally 3-15 nm; and / or, The thickness of the third coating layer is 2-25 nm, and can be optionally 5-25 nm.

46. ​​The battery cell according to any one of claims 19 to 45, characterized in that: The one or more coating layers each independently include one or more selected from pyrophosphate, phosphate and oxide, and the one or more selected from the pyrophosphate, phosphate and oxide are crystalline; Optionally, the crystallinity of the pyrophosphate, the phosphate and the oxide is each independently 10% to 100%, more preferably 50% to 100%.

47. The battery cell according to any one of claims 19 to 46, characterized in that: In the second shell, the weight ratio of the pyrophosphate to the phosphate and the weight ratio of the pyrophosphate to the oxide are each independently 1:3 to 3:1, and may be 1:3 to 1:

1.

48. The battery cell according to any one of claims 19 to 47, characterized in that: The one or more coating layers each independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon; Optionally, in the carbon, the molar ratio of the SP2 carbon to the SP3 carbon is any value in the range of 0.07-13, more preferably any value in the range of 0.1-10, and further preferably any value in the range of 2.0-3.

0.

49. The battery cell according to any one of claims 19 to 48, characterized in that: The one or more coating layers each independently include doped carbon, and the mass content of the doping element in the doped carbon is less than 30%; optionally, the mass content of the doping element in the doped carbon is less than 20%.

50. The battery cell according to any one of claims 19 to 49, characterized in that: The one or more coating layers each independently include doped carbon, in which: The doping element is nitrogen and / or sulfur, and the mass content of the doping element in the doped carbon is 1% to 15%; or, The doping element is phosphorus, boron and / or fluorine, and the mass content of the doping element in the doped carbon is 0.5% to 5%; Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.

51. The battery cell according to any one of claims 19 to 50, characterized in that: The one or more coating layers independently include pyrophosphate, the interplanar spacing of the pyrophosphate is in the range of 0.293-0.470nm, optionally 0.297-0.462nm or 0.293-0.326nm, more optionally 0.300-0.310nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°; and / or, The one or more coating layers independently include phosphate, the interplanar spacing of the phosphate is in the range of 0.244-0.425 nm, optionally 0.345-0.358 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°, optionally 24.25°-26.45°; Optionally, the first coating layer or the second coating layer comprises phosphate.

52. The battery cell according to any one of claims 11 to 51, characterized in that: The lattice change rate of the second positive electrode active material before and after complete lithium deintercalation is 50% or less, optionally 9.8% or less, more optionally 8.1% or less, further optionally 7.5% or less, further optionally 6% or less, further optionally 4% or less, further optionally 3.8% or less, further optionally 2.0%-3.8%; and / or, The Li / Mn antisite defect concentration of the second positive electrode active material is 5.3% or less, optionally 5.1% or less, more optionally 4% or less, further optionally 2.2% or less, further optionally 2% or less, further optionally 1.5%-2.2% or 0.5% or less; and / or, The surface oxygen valence state of the second positive electrode active material is -1.55 or less, optionally -1.82 or less, more optionally -1.88 or less, further optionally -1.90 or less or -1.98 to -1.88, further optionally -1.98 to -1.89, further optionally -1.98 to -1.

90.

53. The battery cell according to any one of claims 1 to 52, characterized in that: The battery cell further includes a negative electrode plate and a separator.

54. A battery, characterized in that: A battery cell comprising the battery cell according to any one of claims 1 to 53.

55. An electrical device, characterized in that: Comprising the battery of claim 54.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and Li-ion secondary battery, and method for producing them

    CN101212061A

  • Secondary cell, cell pack, electric vehicle, power storage system, electric tool, and electronic device

    CN108370064A

  • Electrolyte adaptive to high-nickel ternary positive electrode material

    CN112599856A

  • Electrolyte additive and electrolyte for improving stability of neutral aqueous rechargeable zinc-manganese battery

    CN114335661A

  • Electrolyte, battery monomer, battery and electric equipment

    CN116404256A